Quantum scarred eigenstates in a Rydberg atom chain: Entanglement, breakdown of thermalization, and stability to perturbations - Turner, C J; Michailidis, Alexios; Abanin, D A; Serbyn, Maksym; Papić, Z (Physical Review B)
Recent realization of a kinetically constrained chain of Rydberg atoms by Bernien et al., [Nature (London) 551, 579 (2017)] resulted in the observation of unusual revivals in the many-body quantum dynamics. In our previous work [C. J. Turner et al., Nat. Phys. 14, 745 (2018)], such dynamics was attributed to the existence of “quantum scarred” eigenstates in the many-body spectrum of the experimentally realized model. Here, we present a detailed study of the eigenstate properties of the same model. We find that the majority of the eigenstates exhibit anomalous thermalization: the observable expectation values converge to their Gibbs ensemble values, but parametrically slower compared to the predictions of the eigenstate thermalization hypothesis (ETH). Amidst the thermalizing spectrum, we identify nonergodic eigenstates that strongly violate the ETH, whose number grows polynomially with system size. Previously, the same eigenstates were identified via large overlaps with certain product states, and were used to explain the revivals observed in experiment. Here, we find that these eigenstates, in addition to highly atypical expectation values of local observables, also exhibit subthermal entanglement entropy that scales logarithmically with the system size. Moreover, we identify an additional class of quantum scarred eigenstates, and discuss their manifestations in the dynamics starting from initial product states. We use forward scattering approximation to describe the structure and physical properties of quantum scarred eigenstates. Finally, we discuss the stability of quantum scars to various perturbations. We observe that quantum scars remain robust when the introduced perturbation is compatible with the forward scattering approximation. In contrast, the perturbations which most efficiently destroy quantum scars also lead to the restoration of “canonical” thermalization.

Exceeding the asymptotic limit of polymer drag reduction - Choueiri, George H; Lopez Alonso, Jose M; Hof, Björn (Physical Review Letters)
The drag of turbulent flows can be drastically decreased by adding small amounts of high molecular weight polymers. While drag reduction initially increases with polymer concentration, it eventually saturates to what is known as the maximum drag reduction (MDR) asymptote; this asymptote is generally attributed to the dynamics being reduced to a marginal yet persistent state of subdued turbulent motion. Contrary to this accepted view, we show that, for an appropriate choice of parameters, polymers can reduce the drag beyond the suggested asymptotic limit, eliminating turbulence and giving way to laminar flow. At higher polymer concentrations, however, the laminar state becomes unstable, resulting in a fluctuating flow with the characteristic drag of the MDR asymptote. Our findings indicate that the asymptotic state is hence dynamically disconnected from ordinary turbulence. © 2018 American Physical Society.

Unstable equilibria and invariant manifolds in quasi-two-dimensional Kolmogorov-like flow - Suri, Balachandra; Tithof, Jeffrey; Grigoriev, Roman; Schatz, Michael (Physical Review E)
Recent studies suggest that unstable, nonchaotic solutions of the Navier-Stokes equation may provide deep insights into fluid turbulence. In this article, we present a combined experimental and numerical study exploring the dynamical role of unstable equilibrium solutions and their invariant manifolds in a weakly turbulent, electromagnetically driven, shallow fluid layer. Identifying instants when turbulent evolution slows down, we compute 31 unstable equilibria of a realistic two-dimensional model of the flow. We establish the dynamical relevance of these unstable equilibria by showing that they are closely visited by the turbulent flow. We also establish the dynamical relevance of unstable manifolds by verifying that they are shadowed by turbulent trajectories departing from the neighborhoods of unstable equilibria over large distances in state space.

A homozygous founder mutation in TRAPPC6B associates with a neurodevelopmental disorder characterised by microcephaly epilepsy and autistic features - Marin Valencia, Isaac; Novarino, Gaia; Johansen, Anide; Rosti, Başak; Issa, Mahmoud; Musaev, Damir; Bhat, Gifty; Scott, Eric; Silhavy, Jennifer; Stanley, Valentina; Rosti, Rasim; Gleeson, Jeremy; et al. (Journal of Medical Genetics)
Background: Transport protein particle (TRAPP) is a multisubunit complex that regulates membrane trafficking through the Golgi apparatus. The clinical phenotype associated with mutations in various TRAPP subunits has allowed elucidation of their functions in specific tissues. The role of some subunits in human disease, however, has not been fully established, and their functions remain uncertain. Objective: We aimed to expand the range of neurodevelopmental disorders associated with mutations in TRAPP subunits by exome sequencing of consanguineous families. Methods: Linkage and homozygosity mapping and candidate gene analysis were used to identify homozygous mutations in families. Patient fibroblasts were used to study splicing defect and zebrafish to model the disease. Results: We identified six individuals from three unrelated families with a founder homozygous splice mutation in TRAPPC6B, encoding a core subunit of the complex TRAPP I. Patients manifested a neurodevelopmental disorder characterised by microcephaly, epilepsy and autistic features, and showed splicing defect. Zebrafish trappc6b morphants replicated the human phenotype, displaying decreased head size and neuronal hyperexcitability, leading to a lower seizure threshold. Conclusion: This study provides clinical and functional evidence of the role of TRAPPC6B in brain development and function.

Maps on probability measures preserving certain distances - a survey and some new results - Virosztek, Daniel (Acta Scientiarum Mathematicarum)
Borel probability measures living on metric spaces are fundamental mathematical objects. There are several meaningful distance functions that make the collection of the probability measures living on a certain space a metric space. We are interested in the description of the structure of the isometries of such metric spaces. We overview some of the recent results of the topic and we also provide some new ones concerning the Wasserstein distance. More specifically, we consider the space of all Borel probability measures on the unit sphere of a Euclidean space endowed with the Wasserstein metric W_p for arbitrary p >= 1, and we show that the action of a Wasserstein isometry on the set of Dirac measures is induced by an isometry of the underlying unit sphere.

Statistical mechanics of the uniform electron gas - Lewi, Mathieu; Lieb, Élliott; Seiringer, Robert (Journal de l'Ecole Polytechnique - Mathematiques)
In this paper we define and study the classical Uniform Electron Gas (UEG), a system of infinitely many electrons whose density is constant everywhere in space. The UEG is defined differently from Jellium, which has a positive constant background but no constraint on the density. We prove that the UEG arises in Density Functional Theory in the limit of a slowly varying density, minimizing the indirect Coulomb energy. We also construct the quantum UEG and compare it to the classical UEG at low density.

Agitation modules: Flexible means to accelerate automated freeze substitution - Reipert, Siegfried; Goldammer, Helmuth; Richardson, Christine; Goldberg, Martin; Hawkins, Timothy; Hollergschwandtner, Elena; Kaufmann, Walter; Antreich, Sebastian; Stierhof, York (Journal of Histochemistry and Cytochemistry)
For ultrafast fixation of biological samples to avoid artifacts, high-pressure freezing (HPF) followed by freeze substitution (FS) is preferred over chemical fixation at room temperature. After HPF, samples are maintained at low temperature during dehydration and fixation, while avoiding damaging recrystallization. This is a notoriously slow process. McDonald and Webb demonstrated, in 2011, that sample agitation during FS dramatically reduces the necessary time. Then, in 2015, we (H.G. and S.R.) introduced an agitation module into the cryochamber of an automated FS unit and demonstrated that the preparation of algae could be shortened from days to a couple of hours. We argued that variability in the processing, reproducibility, and safety issues are better addressed using automated FS units. For dissemination, we started low-cost manufacturing of agitation modules for two of the most widely used FS units, the Automatic Freeze Substitution Systems, AFS(1) and AFS2, from Leica Microsystems, using three dimensional (3D)-printing of the major components. To test them, several labs independently used the modules on a wide variety of specimens that had previously been processed by manual agitation, or without agitation. We demonstrate that automated processing with sample agitation saves time, increases flexibility with respect to sample requirements and protocols, and produces data of at least as good quality as other approaches.

Learning equations for extrapolation and control - Sahoo, Subham; Lampert, Christoph; Martius, Georg S (Proceedings of the 35th International Conference on Machine Learning)
We present an approach to identify concise equations from data using a shallow neural network approach. In contrast to ordinary black-box regression, this approach allows understanding functional relations and generalizing them from observed data to unseen parts of the parameter space. We show how to extend the class of learnable equations for a recently proposed equation learning network to include divisions, and we improve the learning and model selection strategy to be useful for challenging real-world data. For systems governed by analytical expressions, our method can in many cases identify the true underlying equation and extrapolate to unseen domains. We demonstrate its effectiveness by experiments on a cart-pendulum system, where only 2 random rollouts are required to learn the forward dynamics and successfully achieve the swing-up task.

Data-dependent stability of stochastic gradient descent - Kuzborskij, Ilja; Lampert, Christoph (Proceedings of the 35 th International Conference on Machine Learning)
We establish a data-dependent notion of algorithmic stability for Stochastic Gradient Descent (SGD), and employ it to develop novel generalization bounds. This is in contrast to previous distribution-free algorithmic stability results for SGD which depend on the worst-case constants. By virtue of the data-dependent argument, our bounds provide new insights into learning with SGD on convex and non-convex problems. In the convex case, we show that the bound on the generalization error depends on the risk at the initialization point. In the non-convex case, we prove that the expected curvature of the objective function around the initialization point has crucial influence on the generalization error. In both cases, our results suggest a simple data-driven strategy to stabilize SGD by pre-screening its initialization. As a corollary, our results allow us to show optimistic generalization bounds that exhibit fast convergence rates for SGD subject to a vanishing empirical risk and low noise of stochastic gradient.

An Austrian proposal for the Classification of Open Access Tuples (COAT) - Distinguish different Open Access types beyond colors - Danowski, Patrick

The convergence of sparsified gradient methods - Alistarh, Dan-Adrian; Hoefler, Torsten; Johansson, Mikael; Konstantinov, Nikola H; Khirirat, Sarit; Renggli, Cedric (Advances in Neural Information Processing Systems 31)
Distributed training of massive machine learning models, in particular deep neural networks, via Stochastic Gradient Descent (SGD) is becoming commonplace. Several families of communication-reduction methods, such as quantization, large-batch methods, and gradient sparsification, have been proposed. To date, gradient sparsification methods--where each node sorts gradients by magnitude, and only communicates a subset of the components, accumulating the rest locally--are known to yield some of the largest practical gains. Such methods can reduce the amount of communication per step by up to three orders of magnitude, while preserving model accuracy. Yet, this family of methods currently has no theoretical justification. This is the question we address in this paper. We prove that, under analytic assumptions, sparsifying gradients by magnitude with local error correction provides convergence guarantees, for both convex and non-convex smooth objectives, for data-parallel SGD. The main insight is that sparsification methods implicitly maintain bounds on the maximum impact of stale updates, thanks to selection by magnitude. Our analysis and empirical validation also reveal that these methods do require analytical conditions to converge well, justifying existing heuristics.

Social network plasticity decreases disease transmission in a eusocial insect - Stroeymeyt, Nathalie; Grasse, Anna V; Crespi, Alessandro; Mersch, Danielle; Cremer, Sylvia; Keller, Laurent (Science)
Animal social networks are shaped by multiple selection pressures, including the need to ensure efficient communication and functioning while simultaneously limiting disease transmission. Social animals could potentially further reduce epidemic risk by altering their social networks in the presence of pathogens, yet there is currently no evidence for such pathogen-triggered responses. We tested this hypothesis experimentally in the ant Lasius niger using a combination of automated tracking, controlled pathogen exposure, transmission quantification, and temporally explicit simulations. Pathogen exposure induced behavioral changes in both exposed ants and their nestmates, which helped contain the disease by reinforcing key transmission-inhibitory properties of the colony's contact network. This suggests that social network plasticity in response to pathogens is an effective strategy for mitigating the effects of disease in social groups.

Nonoptimal gene expression creates latent potential for antibiotic resistance - Palmer, Adam; Chait, Remy P; Kishony, Roy (Molecular Biology and Evolution)
Bacteria regulate genes to survive antibiotic stress, but regulation can be far from perfect. When regulation is not optimal, mutations that change gene expression can contribute to antibiotic resistance. It is not systematically understood to what extent natural gene regulation is or is not optimal for distinct antibiotics, and how changes in expression of specific genes quantitatively affect antibiotic resistance. Here we discover a simple quantitative relation between fitness, gene expression, and antibiotic potency, which rationalizes our observation that a multitude of genes and even innate antibiotic defense mechanisms have expression that is critically nonoptimal under antibiotic treatment. First, we developed a pooled-strain drug-diffusion assay and screened Escherichia coli overexpression and knockout libraries, finding that resistance to a range of 31 antibiotics could result from changing expression of a large and functionally diverse set of genes, in a primarily but not exclusively drug-specific manner. Second, by synthetically controlling the expression of single-drug and multidrug resistance genes, we observed that their fitness-expression functions changed dramatically under antibiotic treatment in accordance with a log-sensitivity relation. Thus, because many genes are nonoptimally expressed under antibiotic treatment, many regulatory mutations can contribute to resistance by altering expression and by activating latent defenses.

Social network plasticity decreases disease transmission in a eusocial insect - Stroeymeyt, Nathalie; Grasse, Anna V; Crespi, Alessandro; Mersch, Danielle; Cremer, Sylvia; Keller, Laurent
Dataset for manuscript 'Social network plasticity decreases disease transmission in a eusocial insect' Compared to previous versions: - raw image files added - correction of URLs within README.txt file

Sensitivity limits of millimeter-wave photonic radiometers based on efficient electro-optic upconverters - Botello, Gabriel; Sedlmeir, Florian; Rueda Sanchez, Alfredo R; Abdalmalak, Kerlos; Brown, Elliott; Leuchs, Gerd; Preu, Sascha; Segovia Vargas, Daniel; Strekalov, Dmitry; Munoz, Luis; Schwefel, Harald (Optica)
Conventional ultra-high sensitivity detectors in the millimeter-wave range are usually cooled as their own thermal noise at room temperature would mask the weak received radiation. The need for cryogenic systems increases the cost and complexity of the instruments, hindering the development of, among others, airborne and space applications. In this work, the nonlinear parametric upconversion of millimeter-wave radiation to the optical domain inside high-quality (Q) lithium niobate whispering-gallery mode (WGM) resonators is proposed for ultra-low noise detection. We experimentally demonstrate coherent upconversion of millimeter-wave signals to a 1550 nm telecom carrier, with a photon conversion efficiency surpassing the state-of-the-art by 2 orders of magnitude. Moreover, a theoretical model shows that the thermal equilibrium of counterpropagating WGMs is broken by overcoupling the millimeter-wave WGM, effectively cooling the upconverted mode and allowing ultra-low noise detection. By theoretically estimating the sensitivity of a correlation radiometer based on the presented scheme, it is found that room-temperature radiometers with better sensitivity than state-of-the-art high-electron-mobility transistor (HEMT)-based radiometers can be designed. This detection paradigm can be used to develop room-temperature instrumentation for radio astronomy, earth observation, planetary missions, and imaging systems.

Contracts for system design - Benveniste, Albert; Nickovic, Dejan; Caillaud, Benoît; Passerone, Roberto; Raclet, Jean Baptiste; Reinkemeier, Philipp; Sangiovanni-Vincentelli, Alberto; Damm, Werner; Henzinger, Thomas A; Larsen, Kim G. (Foundations and Trends in Electronic Design Automation)
Recently, contract-based design has been proposed as an “orthogonal” approach that complements system design methodologies proposed so far to cope with the complexity of system design. Contract-based design provides a rigorous scaffolding for verification, analysis, abstraction/refinement, and even synthesis. A number of results have been obtained in this domain but a unified treatment of the topic that can help put contract-based design in perspective was missing. This monograph intends to provide such a treatment where contracts are precisely defined and characterized so that they can be used in design methodologies with no ambiguity. In particular, this monograph identifies the essence of complex system design using contracts through a mathematical “meta-theory”, where all the properties of the methodology are derived from a very abstract and generic notion of contract. We show that the meta-theory provides deep and illuminating links with existing contract and interface theories, as well as guidelines for designing new theories. Our study encompasses contracts for both software and systems, with emphasis on the latter. We illustrate the use of contracts with two examples: requirement engineering for a parking garage management, and the development of contracts for timing and scheduling in the context of the Autosar methodology in use in the automotive sector.

Coherent-perfect-absorber and laser for bound states in a continuum - Midya, Bikashkali; Konotop, Vladimir (Optics Letters)
It is shown that two fundamentally different phenomena, the bound states in continuum and the spectral singularity (or time-reversed spectral singularity), can occur simultaneously. This can be achieved in a rectangular core dielectric waveguide with an embedded active (or absorbing) layer. In such a system a two-dimensional bound state in a continuum is created in the plane of a waveguide cross section, and it is emitted or absorbed along the waveguide core. The idea can be used for experimental implementation of a laser or a coherent-perfect-absorber for a photonic bound state that resides in a continuous spectrum.

The divergence history of European blue mussel species reconstructed from Approximate Bayesian Computation: The effects of sequencing techniques and sampling strategies - Fraisse, Christelle; Roux, Camille; Gagnaire, Pierre; Romiguier, Jonathan; Faivre, Nicolas; Welch, John; Bierne, Nicolas (PeerJ)
Genome-scale diversity data are increasingly available in a variety of biological systems, and can be used to reconstruct the past evolutionary history of species divergence. However, extracting the full demographic information from these data is not trivial, and requires inferential methods that account for the diversity of coalescent histories throughout the genome. Here, we evaluate the potential and limitations of one such approach. We reexamine a well-known system of mussel sister species, using the joint site frequency spectrum (jSFS) of synonymousmutations computed either fromexome capture or RNA-seq, in an Approximate Bayesian Computation (ABC) framework. We first assess the best sampling strategy (number of: individuals, loci, and bins in the jSFS), and show that model selection is robust to variation in the number of individuals and loci. In contrast, different binning choices when summarizing the jSFS, strongly affect the results: including classes of low and high frequency shared polymorphisms can more effectively reveal recent migration events. We then take advantage of the flexibility of ABC to compare more realistic models of speciation, including variation in migration rates through time (i.e., periodic connectivity) and across genes (i.e., genome-wide heterogeneity in migration rates). We show that these models were consistently selected as the most probable, suggesting that mussels have experienced a complex history of gene flow during divergence and that the species boundary is semi-permeable. Our work provides a comprehensive evaluation of ABC demographic inference in mussels based on the coding jSFS, and supplies guidelines for employing different sequencing techniques and sampling strategies. We emphasize, perhaps surprisingly, that inferences are less limited by the volume of data, than by the way in which they are analyzed.

Can secondary contact following range expansion be distinguished from barriers to gene flow? - Bertl, Johanna; Ringbauer, Harald; Blum, Michaël (PeerJ)
Secondary contact is the reestablishment of gene flow between sister populations that have diverged. For instance, at the end of the Quaternary glaciations in Europe, secondary contact occurred during the northward expansion of the populations which had found refugia in the southern peninsulas. With the advent of multi-locus markers, secondary contact can be investigated using various molecular signatures including gradients of allele frequency, admixture clines, and local increase of genetic differentiation. We use coalescent simulations to investigate if molecular data provide enough information to distinguish between secondary contact following range expansion and an alternative evolutionary scenario consisting of a barrier to gene flow in an isolation-by-distance model. We find that an excess of linkage disequilibrium and of genetic diversity at the suture zone is a unique signature of secondary contact. We also find that the directionality index ψ, which was proposed to study range expansion, is informative to distinguish between the two hypotheses. However, although evidence for secondary contact is usually conveyed by statistics related to admixture coefficients, we find that they can be confounded by isolation-by-distance. We recommend to account for the spatial repartition of individuals when investigating secondary contact in order to better reflect the complex spatio-temporal evolution of populations and species.

Mechanistic framework for cell-intrinsic re-establishment of PIN2 polarity after cell division - Glanc, Matous; Fendrych, Matyas; Friml, Jirí (Nature Plants)
Cell polarity, manifested by the localization of proteins to distinct polar plasma membrane domains, is a key prerequisite of multicellular life. In plants, PIN auxin transporters are prominent polarity markers crucial for a plethora of developmental processes. Cell polarity mechanisms in plants are distinct from other eukaryotes and still largely elusive. In particular, how the cell polarities are propagated and maintained following cell division remains unknown. Plant cytokinesis is orchestrated by the cell plate—a transient centrifugally growing endomembrane compartment ultimately forming the cross wall1. Trafficking of polar membrane proteins is typically redirected to the cell plate, and these will consequently have opposite polarity in at least one of the daughter cells2–5. Here, we provide mechanistic insights into post-cytokinetic re-establishment of cell polarity as manifested by the apical, polar localization of PIN2. We show that the apical domain is defined in a cell-intrinsic manner and that re-establishment of PIN2 localization to this domain requires de novo protein secretion and endocytosis, but not basal-to-apical transcytosis. Furthermore, we identify a PINOID-related kinase WAG1, which phosphorylates PIN2 in vitro6 and is transcriptionally upregulated specifically in dividing cells, as a crucial regulator of post-cytokinetic PIN2 polarity re-establishment.

Language acquisition with communication between learners - Ibsen-Jensen, Rasmus; Tkadlec, Josef; Chatterjee, Krishnendu; Nowak, Martin (Journal of the Royal Society Interface)
We consider a class of students learning a language from a teacher. The situation can be interpreted as a group of child learners receiving input from the linguistic environment. The teacher provides sample sentences. The students try to learn the grammar from the teacher. In addition to just listening to the teacher, the students can also communicate with each other. The students hold hypotheses about the grammar and change them if they receive counter evidence. The process stops when all students have converged to the correct grammar. We study how the time to convergence depends on the structure of the classroom by introducing and evaluating various complexity measures. We find that structured communication between students, although potentially introducing confusion, can greatly reduce some of the complexity measures. Our theory can also be interpreted as applying to the scientific process, where nature is the teacher and the scientists are the students.

Chromatic transitions in the emergence of syntax networks - Corominas-Murtra, Bernat; Fibla, Martí Sànchez; Valverde, Sergi; Solé, Ricard (Royal Society Open Science)
The emergence of syntax during childhood is a remarkable example of how complex correlations unfold in nonlinear ways through development. In particular, rapid transitions seem to occur as children reach the age of two, which seems to separate a two-word, tree-like network of syntactic relations among words from the scale-free graphs associated with the adult, complex grammar. Here, we explore the evolution of syntax networks through language acquisition using the chromatic number, which captures the transition and provides a natural link to standard theories on syntactic structures. The data analysis is compared to a null model of network growth dynamics which is shown to display non-trivial and sensible differences. At a more general level, we observe that the chromatic classes define independent regions of the graph, and thus, can be interpreted as the footprints of incompatibility relations, somewhat as opposed to modularity considerations.

The Dyson equation with linear self-energy: Spectral bands, edges and cusps - Alt, Johannes; Erdös, László; Krüger, Torben H (arXiv)
We study the unique solution $m$ of the Dyson equation \[ -m(z)^{-1} = z - a + S[m(z)] \] on a von Neumann algebra $\mathcal{A}$ with the constraint $Im\,m≥ 0$. Here, $z$ lies in the complex upper half-plane, $a$ is a self-adjoint element of $\mathcal{A}$ and $S$ is a positivity-preserving linear operator on $\mathcal{A}$. We show that $m$ is the Stieltjes transform of a compactly supported $\mathcal{A}$-valued measure on $\mathbb{R}$. Under suitable assumptions, we establish that this measure has a uniformly $1/3$-Hölder continuous density with respect to the Lebesgue measure, which is supported on finitely many intervals, called bands. In fact, the density is analytic inside the bands with a square-root growth at the edges and internal cubic root cusps whenever the gap between two bands vanishes. The shape of these singularities is universal and no other singularity may occur. We give a precise asymptotic description of $m$ near the singular points. These asymptotics generalize the analysis at the regular edges given in the companion paper on the Tracy-Widom universality for the edge eigenvalue statistics for correlated random matrices [arXiv:1804.07744] and they play a key role in the proof of the Pearcey universality at the cusp for Wigner-type matrices [arXiv:1809.03971,arXiv:1811.04055]. We also extend the finite dimensional band mass formula from [arXiv:1804.07744] to the von Neumann algebra setting by showing that the spectral mass of the bands is topologically rigid under deformations and we conclude that these masses are quantized in some important cases.

Convex fair partitions into arbitrary number of pieces - Akopyan, Arseniy; Avvakumov, Sergey; Karasev, Roman
We prove that any convex body in the plane can be partitioned into m convex parts of equal areas and perimeters for any integer m≥2; this result was previously known for prime powers m=pk. We also give a higher-dimensional generalization.

The free boundary Schur process and applications I - Betea, Dan; Bouttier, Jeremie; Nejjar, Peter; Vuletic, Mirjana (Annales Henri Poincare)
We investigate the free boundary Schur process, a variant of the Schur process introduced by Okounkov and Reshetikhin, where we allow the first and the last partitions to be arbitrary (instead of empty in the original setting). The pfaffian Schur process, previously studied by several authors, is recovered when just one of the boundary partitions is left free. We compute the correlation functions of the process in all generality via the free fermion formalism, which we extend with the thorough treatment of “free boundary states.” For the case of one free boundary, our approach yields a new proof that the process is pfaffian. For the case of two free boundaries, we find that the process is not pfaffian, but a closely related process is. We also study three different applications of the Schur process with one free boundary: fluctuations of symmetrized last passage percolation models, limit shapes and processes for symmetric plane partitions and for plane overpartitions.

Graph matching problems for GraphFlow – 6D Large Displacement Scene Flow - Alhaija, Hassan; Sellent, Anita; Kondermann, Daniel; Rother, Carsten
Graph matching problems for large displacement optical flow of RGB-D images.
Keywords: graph matching; quadratic assignment problem<

Emerald Austrian Publications 2013-2017 - Villányi, Márton
Data on Austrian open access publication output at Emerald from 2013-2017 including data analysis.
Keywords: Publication analysis; Bibliography; Open Access

IOP Austrian Publications 2012-2015 - Villányi, Márton
Data on Austrian open access publication output at IOP from 2012-2015 including data analysis.
Keywords: Publication analysis; Bibliography; Open Access

Data Check IOP Scopus vs. Publisher - Villányi, Márton
Comparison of Scopus' and publisher's data on Austrian publication output at IOP.
Keywords: Publication analysis; Bibliography; Open Access

Lizenzverträge mit Open-Access-Komponenten an österreichischen Bibliotheken - Villányi, Márton
Consortial subscription contracts regulate the digital access to publications between publishers and scientific libraries. However, since a couple of years the tendency towards a freely accessible publishing (Open Access) intensifies. As a consequence of this trend the contractual relationship between licensor and licensee is gradually changing as well: More and more contracts exercise influence on open access publishing. The present study attempts to compare Austrian examples of consortial licence contracts, which include components of open access. It describes the difference between pure subscription contracts and differing innovative deals including open access components. Thereby it becomes obvious that for the evaluation of this licence contracts new methods are needed. An essential new element of such analyses is the evaluation of the open access publication numbers. So this study tries to carry out such publication analyses for Austrian open access deals focusing on quantitative questions: How does the number of publications evolve? How does the open access share change? Publications reports of the publishers and database queries from Scopus form the data basis. The analysis of the data points out that differing approaches of contracts result in highly divergent results: Particular deals can prioritize a saving in costs or else the increase of the open access rate. It is to be assumed that within the following years further numerous open access deals will be negotiated. The finding of this study shall provide guidance.

Fluorescence lifetime analysis of FLIM X16 TCSPC data - Hauschild, Robert
Script to perform a simple exponential lifetime fit of a ROI on time stacks acquired with a FLIM X16 TCSPC detector (+example data)
Keywords: FLIM; FRET; fluorescence lifetime imaging

Taylor&Francis Austrian Publications 2013-2017 - Villányi, Márton
Data on Austrian open access publication output at Taylor&Francis from 2013-2017 including data analysis.
Keywords: Publication analysis; Bibliography; Open Access

Springer Austrian Publications 2013-2016 - Villányi, Márton
Data on Austrian open access publication output at Springer from 2013-2016 including data analysis.
Keywords: Publication analysis; Bibliography; Open Access

SAGE Austrian Publications 2013-2017 - Villányi, Márton
Data on Austrian open access publication output at SAGE from 2013-2017 including data analysis.
Keywords: Publication analysis; Bibliography; Open Access

RSC Austrian Publications 2013-2017 - Villányi, Márton
Data on Austrian open access publication output at RSC from 2013-2017 including data analysis.
Keywords: Publication analysis; Bibliography; Open Access

Data Check T&F Scopus vs. FWF - Villányi, Márton
Comparison of Scopus' and FWF's data on Austrian publication output at T&F.
Keywords: Publication analysis; Bibliography; Open Access

Data Check RSC Scopus vs. FWF - Villányi, Márton
Comparison of Scopus' and FWF's data on Austrian publication output at RSC.
Keywords: Publication analysis; Bibliography; Open Access

Nonlinear decoding of a complex movie from the mammalian retina - Botella Soler, Vicent; Deny, Stephane; Martius, Georg S; Marre, Olivier; Tkacik, Gasper (PLoS Computational Biology)
Retina is a paradigmatic system for studying sensory encoding: the transformation of light into spiking activity of ganglion cells. The inverse problem, where stimulus is reconstructed from spikes, has received less attention, especially for complex stimuli that should be reconstructed “pixel-by-pixel”. We recorded around a hundred neurons from a dense patch in a rat retina and decoded movies of multiple small randomly-moving discs. We constructed nonlinear (kernelized and neural network) decoders that improved significantly over linear results. An important contribution to this was the ability of nonlinear decoders to reliably separate between neural responses driven by locally fluctuating light signals, and responses at locally constant light driven by spontaneous-like activity. This improvement crucially depended on the precise, non-Poisson temporal structure of individual spike trains, which originated in the spike-history dependence of neural responses. We propose a general principle by which downstream circuitry could discriminate between spontaneous and stimulus-driven activity based solely on higher-order statistical structure in the incoming spike trains.

Autoregulation of mazEF expression underlies growth heterogeneity in bacterial populations - Nikolic, Nela; Bergmiller, Tobias; Vandervelde, Alexandra; Albanese, Tanino; Gelens, Lendert; Moll, Isabella (Nucleic Acids Research)
The MazF toxin sequence-specifically cleaves single-stranded RNA upon various stressful conditions, and it is activated as a part of the mazEF toxin–antitoxin module in Escherichia coli. Although autoregulation of mazEF expression through the MazE antitoxin-dependent transcriptional repression has been biochemically characterized, less is known about post-transcriptional autoregulation, as well as how both of these autoregulatory features affect growth of single cells during conditions that promote MazF production. Here, we demonstrate post-transcriptional autoregulation of mazF expression dynamics by MazF cleaving its own transcript. Single-cell analyses of bacterial populations during ectopic MazF production indicated that two-level autoregulation of mazEF expression influences cell-to-cell growth rate heterogeneity. The increase in growth rate heterogeneity is governed by the MazE antitoxin, and tuned by the MazF-dependent mazF mRNA cleavage. Also, both autoregulatory features grant rapid exit from the stress caused by mazF overexpression. Time-lapse microscopy revealed that MazF-mediated cleavage of mazF mRNA leads to increased temporal variability in length of individual cells during ectopic mazF overexpression, as explained by a stochastic model indicating that mazEF mRNA cleavage underlies temporal fluctuations in MazF levels during stress.

Evolution of gene dosage on the Z-chromosome of schistosome parasites - Picard, Marion A; Cosseau, Celine; Ferré, Sabrina; Quack, Thomas; Grevelding, Christoph; Couté, Yohann; Vicoso, Beatriz (eLife)
XY systems usually show chromosome-wide compensation of X-linked genes, while in many ZW systems, compensation is restricted to a minority of dosage-sensitive genes. Why such differences arose is still unclear. Here, we combine comparative genomics, transcriptomics and proteomics to obtain a complete overview of the evolution of gene dosage on the Z-chromosome of Schistosoma parasites. We compare the Z-chromosome gene content of African (Schistosoma mansoni and S. haematobium) and Asian (S. japonicum) schistosomes and describe lineage-specific evolutionary strata. We use these to assess gene expression evolution following sex-linkage. The resulting patterns suggest a reduction in expression of Z-linked genes in females, combined with upregulation of the Z in both sexes, in line with the first step of Ohno’s classic model of dosage compensation evolution. Quantitative proteomics suggest that post-transcriptional mechanisms do not play a major role in balancing the expression of Z-linked genes.

Nonlinear decoding of a complex movie from the mammalian retina - Deny, Stephane; Marre, Olivier; Botella-Soler, Vicente; Martius, Georg S; Tkacik, Gasper
This package contains data for the publication "Nonlinear decoding of a complex movie from the mammalian retina" by Deny S. et al, PLOS Comput Biol (2018). The data consists of (i) 91 spike sorted, isolated rat retinal ganglion cells that pass stability and quality criteria, recorded on the multi-electrode array, in response to the presentation of the complex movie with many randomly moving dark discs. The responses are represented as 648000 x 91 binary matrix, where the first index indicates the timebin of duration 12.5 ms, and the second index the neural identity. The matrix entry is 0/1 if the neuron didn't/did spike in the particular time bin. (ii) README file and a graphical illustration of the structure of the experiment, specifying how the 648000 timebins are split into epochs where 1, 2, 4, or 10 discs were displayed, and which stimulus segments are exact repeats or unique ball trajectories. (iii) a 648000 x 400 matrix of luminance traces for each of the 20 x 20 positions ("sites") in the movie frame, with time that is locked to the recorded raster. The luminance traces are produced as described in the manuscript by filtering the raw disc movie with a small gaussian spatial kernel.
Keywords: retina; decoding; regression; neural networks; complex stimulus

Input files and scripts from "Evolution of gene dosage on the Z-chromosome of schistosome parasites" by Picard M.A.L., et al (2018) - Vicoso, Beatriz
Input files and scripts from "Evolution of gene dosage on the Z-chromosome of schistosome parasites" by Picard M.A.L., et al (2018).
Keywords: schistosoma; Z-chromosome; gene expression

Data and Python scripts supporting Python package FAPS - Ellis, Thomas
Data and scripts are provided in support of the manuscript "Efficient inference of paternity and sibship inference given known maternity via hierarchical clustering", and the associated Python package FAPS, available from www.github.com/ellisztamas/faps. Simulation scripts cover: 1. Performance under different mating scenarios. 2. Comparison with Colony2. 3. Effect of changing the number of Monte Carlo draws The final script covers the analysis of half-sib arrays from wild-pollinated seed in an Antirrhinum majus hybrid zone.

Time-lapse microscopy data - Bergmiller, Tobias; Nikolic, Nela
Nela Nikolic, Tobias Bergmiller, Alexandra Vandervelde, Tanino G. Albanese, Lendert Gelens, and Isabella Moll (2018) “Autoregulation of mazEF expression underlies growth heterogeneity in bacterial populations” Nucleic Acids Research, doi: 10.15479/AT:ISTA:74; microscopy experiments by Tobias Bergmiller; image and data analysis by Nela Nikolic.
Keywords: microscopy; microfluidics

Statistical mechanics for metabolic networks during steady state growth - De Martino, Daniele; Mc, Andersson Anna; Bergmiller, Tobias; Guet, Calin C; Tkacik, Gasper (Nature Communications)
Which properties of metabolic networks can be derived solely from stoichiometry? Predictive results have been obtained by flux balance analysis (FBA), by postulating that cells set metabolic fluxes to maximize growth rate. Here we consider a generalization of FBA to single-cell level using maximum entropy modeling, which we extend and test experimentally. Specifically, we define for Escherichia coli metabolism a flux distribution that yields the experimental growth rate: the model, containing FBA as a limit, provides a better match to measured fluxes and it makes a wide range of predictions: on flux variability, regulation, and correlations; on the relative importance of stoichiometry vs. optimization; on scaling relations for growth rate distributions. We validate the latter here with single-cell data at different sub-inhibitory antibiotic concentrations. The model quantifies growth optimization as emerging from the interplay of competitive dynamics in the population and regulation of metabolism at the level of single cells.

Supporting materials "STATISTICAL MECHANICS FOR METABOLIC NETWORKS IN STEADY-STATE GROWTH" - De Martino, Daniele; Tkacik, Gasper
Supporting material to the article STATISTICAL MECHANICS FOR METABOLIC NETWORKS IN STEADY-STATE GROWTH boundscoli.dat Flux Bounds of the E. coli catabolic core model iAF1260 in a glucose limited minimal medium. polcoli.dat Matrix enconding the polytope of the E. coli catabolic core model iAF1260 in a glucose limited minimal medium, obtained from the soichiometric matrix by standard linear algebra (reduced row echelon form). ellis.dat Approximate Lowner-John ellipsoid rounding the polytope of the E. coli catabolic core model iAF1260 in a glucose limited minimal medium obtained with the Lovasz method. point0.dat Center of the approximate Lowner-John ellipsoid rounding the polytope of the E. coli catabolic core model iAF1260 in a glucose limited minimal medium obtained with the Lovasz method. lovasz.cpp This c++ code file receives in input the polytope of the feasible steady states of a metabolic network, (matrix and bounds), and it gives in output an approximate Lowner-John ellipsoid rounding the polytope with the Lovasz method NB inputs are referred by defaults to the catabolic core of the E.Coli network iAF1260. For further details we refer to PLoS ONE 10.4 e0122670 (2015). sampleHRnew.cpp This c++ code file receives in input the polytope of the feasible steady states of a metabolic network, (matrix and bounds), the ellipsoid rounding the polytope, a point inside and it gives in output a max entropy sampling at fixed average growth rate of the steady states by performing an Hit-and-Run Monte Carlo Markov chain. NB inputs are referred by defaults to the catabolic core of the E.Coli network iAF1260. For further details we refer to PLoS ONE 10.4 e0122670 (2015).
Keywords: metabolic networks; e.coli core; maximum entropy; monte carlo markov chain sampling; ellipsoidal rounding

Complex history and differentiation patterns of the t-haplotype, a mouse meiotic driver - Kelemen, Réka K; Vicoso, Beatriz (Genetics)
The t-haplotype, a mouse meiotic driver found on chromosome 17, has been a model for autosomal segregation distortion for close to a century, but several questions remain regarding its biology and evolutionary history. A recently published set of population genomics resources for wild mice includes several individuals heterozygous for the t-haplotype, which we use to characterize this selfish element at the genomic and transcriptomic level. Our results show that large sections of the t-haplotype have been replaced by standard homologous sequences, possibly due to occasional events of recombination, and that this complicates the inference of its history. As expected for a long genomic segment of very low recombination, the t-haplotype carries an excess of fixed nonsynonymous mutations compared to the standard chromosome. This excess is stronger for regions that have not undergone recent recombination, suggesting that occasional gene flow between the t and the standard chromosome may provide a mechanism to regenerate coding sequences that have accumulated deleterious mutations. Finally, we find that t-complex genes with altered expression largely overlap with deleted or amplified regions, and that carrying a t-haplotype alters the testis expression of genes outside of the t-complex, providing new leads into the pathways involved in the biology of this segregation distorter.

Construction of arbitrarily strong amplifiers of natural selection using evolutionary graph theory - Pavlogiannis, Andreas; Tkadlec, Josef; Chatterjee, Krishnendu; Nowak, Martin A. (Communications Biology)
Because of the intrinsic randomness of the evolutionary process, a mutant with a fitness advantage has some chance to be selected but no certainty. Any experiment that searches for advantageous mutants will lose many of them due to random drift. It is therefore of great interest to find population structures that improve the odds of advantageous mutants. Such structures are called amplifiers of natural selection: they increase the probability that advantageous mutants are selected. Arbitrarily strong amplifiers guarantee the selection of advantageous mutants, even for very small fitness advantage. Despite intensive research over the past decade, arbitrarily strong amplifiers have remained rare. Here we show how to construct a large variety of them. Our amplifiers are so simple that they could be useful in biotechnology, when optimizing biological molecules, or as a diagnostic tool, when searching for faster dividing cells or viruses. They could also occur in natural population structures.

Supplementary Files for "Pleiotropy modulates the efficacy of selection in Drosophila melanogaster" - Fraisse, Christelle
File S1. Variant Calling Format file of the ingroup: 197 haploid sequences of D. melanogaster from Zambia (Africa) aligned to the D. melanogaster 5.57 reference genome. File S2. Variant Calling Format file of the outgroup: 1 haploid sequence of D. simulans aligned to the D. melanogaster 5.57 reference genome. File S3. Annotations of each transcript in coding regions with SNPeff: Ps (# of synonymous polymorphic sites); Pn (# of non-synonymous polymorphic sites); Ds (# of synonymous divergent sites); Dn (# of non-synonymous divergent sites); DoS; ⍺ MK . All variants were included. File S4. Annotations of each transcript in non-coding regions with SNPeff: Ps (# of synonymous polymorphic sites); Pu (# of UTR polymorphic sites); Ds (# of synonymous divergent sites); Du (# of UTR divergent sites); DoS; ⍺ MK . All variants were included. File S5. Annotations of each transcript in coding regions with SNPGenie: Ps (# of synonymous polymorphic sites); πs (synonymous diversity); Ss_p (total # of synonymous sites in the polymorphism data); Pn (# of non-synonymous polymorphic sites); πn (non-synonymous diversity); Sn_p (total # of non-synonymous sites in the polymorphism data); Ds (# of synonymous divergent sites); ks (synonymous evolutionary rate); Ss_d (total # of synonymous sites in the divergence data); Dn (# of non-synonymous divergent sites); kn (non-synonymous evolutionary rate); Sn_d (total # of non- synonymous sites in the divergence data); DoS; ⍺ MK . All variants were included. File S6. Gene expression values (RPKM summed over all transcripts) for each sample. Values were quantile-normalized across all samples. File S7. Final dataset with all covariates, ⍺ MK , ωA MK and DoS for coding sites, excluding variants below 5% frequency. File S8. Final dataset with all covariates, ⍺ MK , ωA MK and DoS for non-coding sites, excluding variants below 5% frequency. File S9. Final dataset with all covariates, ⍺ EWK , ωA EWK and deleterious SFS for coding sites obtained with the Eyre-Walker and Keightley method on binned data and using all variants.
Keywords: (mal)adaptation; pleiotropy; selective constraint; evo-devo; gene expression; Drosophila melanogaster

Dyson equation and eigenvalue statistics of random matrices - Alt, Johannes
The eigenvalue density of many large random matrices is well approximated by a deterministic measure, the self-consistent density of states. In the present work, we show this behaviour for several classes of random matrices. In fact, we establish that, in each of these classes, the self-consistent density of states approximates the eigenvalue density of the random matrix on all scales slightly above the typical eigenvalue spacing. For large classes of random matrices, the self-consistent density of states exhibits several universal features. We prove that, under suitable assumptions, random Gram matrices and Hermitian random matrices with decaying correlations have a 1/3-Hölder continuous self-consistent density of states ρ on R, which is analytic, where it is positive, and has either a square root edge or a cubic root cusp, where it vanishes. We, thus, extend the validity of the corresponding result for Wigner-type matrices from [4, 5, 7]. We show that ρ is determined as the inverse Stieltjes transform of the normalized trace of the unique solution m(z) to the Dyson equation −m(z) −1 = z − a + S[m(z)] on C N×N with the constraint Im m(z) ≥ 0. Here, z lies in the complex upper half-plane, a is a self-adjoint element of C N×N and S is a positivity-preserving operator on C N×N encoding the first two moments of the random matrix. In order to analyze a possible limit of ρ for N → ∞ and address some applications in free probability theory, we also consider the Dyson equation on infinite dimensional von Neumann algebras. We present two applications to random matrices. We first establish that, under certain assumptions, large random matrices with independent entries have a rotationally symmetric self-consistent density of states which is supported on a centered disk in C. Moreover, it is infinitely often differentiable apart from a jump on the boundary of this disk. Second, we show edge universality at all regular (not necessarily extreme) spectral edges for Hermitian random matrices with decaying correlations.

Effect of a magnetic field on molecule–solvent angular momentum transfer - Rzadkowski, Wojciech; Lemeshko, Mikhail (The Journal of Chemical Physics)
Recently it was shown that a molecule rotating in a quantum solvent can be described in terms of the “angulon” quasiparticle [M. Lemeshko, Phys. Rev. Lett. 118, 095301 (2017)]. Here we extend the angulon theory to the case of molecules possessing an additional spin-1/2 degree of freedom and study the behavior of the system in the presence of a static magnetic field. We show that exchange of angular momentum between the molecule and the solvent can be altered by the field, even though the solvent itself is non-magnetic. In particular, we demonstrate a possibility to control resonant emission of phonons with a given angular momentum using a magnetic field.

Water surface wavelets - Jeschke, Stefan; Skrivan, Tomas; Mueller Fischer, Matthias; Chentanez, Nuttapong; Macklin, Miles; Wojtan, Christopher J (ACM Transactions on Graphics)
The current state of the art in real-time two-dimensional water wave simulation requires developers to choose between efficient Fourier-based methods, which lack interactions with moving obstacles, and finite-difference or finite element methods, which handle environmental interactions but are significantly more expensive. This paper attempts to bridge this long-standing gap between complexity and performance, by proposing a new wave simulation method that can faithfully simulate wave interactions with moving obstacles in real time while simultaneously preserving minute details and accommodating very large simulation domains. Previous methods for simulating 2D water waves directly compute the change in height of the water surface, a strategy which imposes limitations based on the CFL condition (fast moving waves require small time steps) and Nyquist's limit (small wave details require closely-spaced simulation variables). This paper proposes a novel wavelet transformation that discretizes the liquid motion in terms of amplitude-like functions that vary over space, frequency, and direction, effectively generalizing Fourier-based methods to handle local interactions. Because these new variables change much more slowly over space than the original water height function, our change of variables drastically reduces the limitations of the CFL condition and Nyquist limit, allowing us to simulate highly detailed water waves at very large visual resolutions. Our discretization is amenable to fast summation and easy to parallelize. We also present basic extensions like pre-computed wave paths and two-way solid fluid coupling. Finally, we argue that our discretization provides a convenient set of variables for artistic manipulation, which we illustrate with a novel wave-painting interface.

Diagrammatic Monte Carlo approach to angular momentum in quantum many-particle systems - Bighin, Giacomo; Tscherbul, Timur; Lemeshko, Mikhail (Physical Review Letters)
We introduce a diagrammatic Monte Carlo approach to angular momentum properties of quantum many-particle systems possessing a macroscopic number of degrees of freedom. The treatment is based on a diagrammatic expansion that merges the usual Feynman diagrams with the angular momentum diagrams known from atomic and nuclear structure theory, thereby incorporating the non-Abelian algebra inherent to quantum rotations. Our approach is applicable at arbitrary coupling, is free of systematic errors and of finite-size effects, and naturally provides access to the impurity Green function. We exemplify the technique by obtaining an all-coupling solution of the angulon model; however, the method is quite general and can be applied to a broad variety of systems in which particles exchange quantum angular momentum with their many-body environment.

Diagrammatic Monte Carlo approach to rotating molecular impurities - Bighin, Giacomo; Tscherbul, Timur; Lemeshko, Mikhail (Physical Review Letters)
We introduce a Diagrammatic Monte Carlo (DiagMC) approach to complex molecular impurities with rotational degrees of freedom interacting with a many-particle environment. The treatment is based on the diagrammatic expansion that merges the usual Feynman diagrams with the angular momentum diagrams known from atomic and nuclear structure theory, thereby incorporating the non-Abelian algebra inherent to quantum rotations. Our approach works at arbitrary coupling, is free of systematic errors and of finite size effects, and naturally provides access to the impurity Green function. We exemplify the technique by obtaining an all-coupling solution of the angulon model, however, the method is quite general and can be applied to a broad variety of quantum impurities possessing angular momentum degrees of freedom.

A functional study of AUXILIN LIKE1 and 2 two putative clathrin uncoating factors in Arabidopsis - Adamowski, Maciek; Narasimhan, Madhumitha; Kania, Urszula; Glanc, Matous; De Jaeger, Geert; Friml, Jirí (The Plant Cell)
Clathrin-mediated endocytosis (CME) is a cellular trafficking process in which cargoes and lipids are internalized from the plasma membrane into vesicles coated with clathrin and adaptor proteins. CME is essential for many developmental and physiological processes in plants, but its underlying mechanism is not well characterised compared to that in yeast and animal systems. Here, we searched for new factors involved in CME in Arabidopsis thaliana by performing Tandem Affinity Purification of proteins that interact with clathrin light chain, a principal component of the clathrin coat. Among the confirmed interactors, we found two putative homologues of the clathrin-coat uncoating factor auxilin previously described in non-plant systems. Overexpression of AUXILIN-LIKE1 and AUXILIN-LIKE2 in A. thaliana caused an arrest of seedling growth and development. This was concomitant with inhibited endocytosis due to blocking of clathrin recruitment after the initial step of adaptor protein binding to the plasma membrane. By contrast, auxilin-like(1/2) loss-of-function lines did not present endocytosis-related developmental or cellular phenotypes under normal growth conditions. This work contributes to the on-going characterization of the endocytotic machinery in plants and provides a robust tool for conditionally and specifically interfering with CME in A. thaliana.

Lymph node blood vessels provide exit routes for metastatic tumor cell dissemination in mice - Brown, Markus; Assen, Frank P; Leithner, Alexander F; Abe, Jun; Schachner, Helga; Asfour, Gabriele; Bagó Horváth, Zsuzsanna; Stein, Jens; Uhrin, Pavel; Sixt, Michael K; Kerjaschki, Dontscho (Science)
During metastasis, malignant cells escape the primary tumor, intravasate lymphatic vessels, and reach draining sentinel lymph nodes before they colonize distant organs via the blood circulation. Although lymph node metastasis in cancer patients correlates with poor prognosis, evidence is lacking as to whether and how tumor cells enter the bloodstream via lymph nodes. To investigate this question, we delivered carcinoma cells into the lymph nodes of mice by microinfusing the cells into afferent lymphatic vessels. We found that tumor cells rapidly infiltrated the lymph node parenchyma, invaded blood vessels, and seeded lung metastases without involvement of the thoracic duct. These results suggest that the lymph node blood vessels can serve as an exit route for systemic dissemination of cancer cells in experimental mouse models. Whether this form of tumor cell spreading occurs in cancer patients remains to be determined.

The branched chain amino acids in autism spectrum disorders - Tarlungeanu, Dora-Clara
Autism spectrum disorders (ASD) are a group of genetic disorders often overlapping with other neurological conditions. Despite the remarkable number of scientific breakthroughs of the last 100 years, the treatment of neurodevelopmental disorders (e.g. autism spectrum disorder, intellectual disability, epilepsy) remains a great challenge. Recent advancements in geno mics, like whole-exome or whole-genome sequencing, have enabled scientists to identify numerous mutations underlying neurodevelopmental disorders. Given the few hundred risk genes that were discovered, the etiological variability and the heterogeneous phenotypic outcomes, the need for genotype -along with phenotype- based diagnosis of individual patients becomes a requisite. Driven by this rationale, in a previous study our group described mutations, identified via whole - exome sequencing, in the gene BCKDK – encoding for a key regulator of branched chain amin o acid (BCAA) catabolism - as a cause of ASD. Following up on the role of BCAAs, in the study described here we show that the solute carrier transporter 7a5 (SLC7A5), a large neutral amino acid transporter localized mainly at the blood brain barrier (BBB), has an essential role in maintaining normal levels of brain BCAAs. In mice, deletion of Slc7a5 from the endothelial cells of the BBB leads to atypical brain amino acid profile, abnormal mRNA translation and severe neurolo gical abnormalities. Additionally, deletion of Slc7a5 from the neural progenitor cell population leads to microcephaly. Interestingly, we demonstrate that BCAA intracerebroventricular administration ameliorates abnormal behaviors in adult mutant mice. Furthermore, whole - exome sequencing of patients diagnosed with neurological dis o r ders helped us identify several patients with autistic traits, microcephaly and motor delay carrying deleterious homozygous mutations in the SLC7A5 gene. In conclusion, our data elucidate a neurological syndrome defined by SLC7A5 mutations and support an essential role for t he BCAA s in human bra in function. Together with r ecent studies (described in chapter two) that have successfully made the transition into clinical practice, our findings on the role of B CAAs might have a crucial impact on the development of novel individualized therapeutic strategies for ASD.

From the left to the right: A tale of asymmetries, environments, and hippocampal development - Case, Matthew J
Asymmetries have long been known about in the central nervous system. From gross anatomical differences, such as the presence of the parapineal organ in only one hemisphere of the developing zebrafish, to more subtle differences in activity between both hemispheres, as seen in freely roaming animals or human participants under PET and fMRI imaging analysis. The presence of asymmetries has been demonstrated to have huge behavioural implications, with their disruption often leading to the generation of neurological disorders, memory problems, changes in personality, and in an organism's health and well-being. For my Ph.D. work I aimed to tackle two important avenues of research. The first being the process of input-side dependency in the hippocampus, with the goal of finding a key gene responsible for its development (Gene X). The second project was to do with experience-induced laterality formation in the hippocampus. Specifically, how laterality in the synapse density of the CA1 stratum radiatum (s.r.) could be induced purely through environmental enrichment. Through unilateral tracer injections into the CA3, I was able to selectively measure the properties of synapses within the CA1 and investigate how they differed based upon which hemisphere the presynaptic neurone originated. Having found the existence of a previously unreported reversed (left-isomerism) i.v. mutant, through morpholocal examination of labelled terminals in the CA1 s.r., I aimed to elucidate a key gene responsible for the process of left or right determination of inputs to the CA1 s.r.. This work relates to the previous finding of input-side dependent asymmetry in the wild-type rodent, where the origin of the projecting neurone to the CA1 will determine the morphology of a synapse, to a greater degree than the hemisphere in which the projection terminates. Using left- and right-isomerism i.v. mice, in combination with whole genome sequence analysis, I highlight Ena/VASP-like (Evl) as a potential target for Gene X. In relation to this topic, I also highlight my work in the recently published paper of how knockout of PirB can lead to a lack of input-side dependency in the murine hippocampus. For the second question, I show that the environmental enrichment paradigm will lead to an asymmetry in the synapse densities in the hippocampus of mice. I also highlight that the nature of the enrichment is of less consequence than the process of enrichment itself. I demonstrate that the CA3 region will dramatically alter its projection targets, in relation to environmental stimulation, with the asymmetry in synaptic density, caused by enrichment, relying heavily on commissural fibres. I also highlight the vital importance of input-side dependent asymmetry, as a necessary component of experience-dependent laterality formation in the CA1 s.r.. However, my results suggest that it isn't the only cause, as there appears to be a CA1 dependent mechanism also at play. Upon further investigation, I highlight the significant, and highly important, finding that the changes seen in the CA1 s.r. were predominantly caused through projections from the left-CA3, with the right-CA3 having less involvement in this mechanism.

Role of genomic imprinting in cerebral cortex development - Laukoter, Susanne
Genomic imprinting is an epigenetic process that leads to parent of origin-specific gene expression in a subset of genes. Imprinted genes are essential for brain development, and deregulation of imprinting is associated with neurodevelopmental diseases and the pathogenesis of psychiatric disorders. However, the cell-type specificity of imprinting at single cell resolution, and how imprinting and thus gene dosage regulates neuronal circuit assembly is still largely unknown. Here, MADM (Mosaic Analysis with Double Markers) technology was employed to assess genomic imprinting at single cell level. By visualizing MADM-induced uniparental disomies (UPDs) in distinct colors at single cell level in genetic mosaic animals, this experimental paradigm provides a unique quantitative platform to systematically assay the UPD-mediated imbalances in imprinted gene expression at unprecedented resolution. An experimental pipeline based on FACS, RNA-seq and bioinformatics analysis was established and applied to systematically map cell-type-specific ‘imprintomes’ in the mouse brain. The results revealed that parental-specific expression of imprinted genes per se is rarely cell-type-specific even at the individual cell level. Conversely, when we extended the comparison to downstream responses resulting from imbalanced imprinted gene expression, we discovered an unexpectedly high degree of cell-type specificity. Furthermore, we determined a novel function of genomic imprinting in cortical astrocyte production and in olfactory bulb (OB) granule cell generation. These results suggest important functional implication of genomic imprinting for generating cell-type diversity in the brain. In addition, MADM provides a powerful tool to study candidate genes by concomitant genetic manipulation and fluorescent labelling of single cells. MADM-based candidate gene approach was utilized to identify potential imprinted genes involved in the generation of cortical astrocytes and OB granule cells. We investigated p57Kip2, a maternally expressed gene and known cell cycle regulator. Although we found that p57Kip2 does not play a role in these processes, we detected an unexpected function of the paternal allele previously thought to be silent. Finally, we took advantage of a key property of MADM which is to allow unambiguous investigation of environmental impact on single cells. The experimental pipeline based on FACS and RNA-seq analysis of MADM-labeled cells was established to probe the functional differences of single cell loss of gene function compared to global loss of function on a transcriptional level. With this method, both common and distinct responses were isolated due to cell-autonomous and non-autonomous effects acting on genotypically identical cells. As a result, transcriptional changes were identified which result solely from the surrounding environment. Using the MADM technology to study genomic imprinting at single cell resolution, we have identified cell-type-specific gene expression, novel gene function and the impact of environment on single cell transcriptomes. Together, these provide important insights to the understanding of mechanisms regulating cell-type specificity and thus diversity in the brain.

Branched actin networks in dendritic cell biology - Leithner, Alexander F
In the here presented thesis, we explore the role of branched actin networks in cell migration and antigen presentation, the two most relevant processes in dendritic cell biology. Branched actin networks construct lamellipodial protrusions at the leading edge of migrating cells. These are typically seen as adhesive structures, which mediate force transduction to the extracellular matrix that leads to forward locomotion. We ablated Arp2/3 nucleation promoting factor WAVE in DCs and found that the resulting cells lack lamellipodial protrusions. Instead, depending on the maturation state, one or multiple filopodia were formed. By challenging these cells in a variety of migration assays we found that lamellipodial protrusions are dispensable for the locomotion of leukocytes and actually dampen the speed of migration. However, lamellipodia are critically required to negotiate complex environments that DCs experience while they travel to the next draining lymph node. Taken together our results suggest that leukocyte lamellipodia have rather a sensory- than a force transducing function. Furthermore, we show for the first time structure and dynamics of dendritic cell F-actin at the immunological synapse with naïve T cells. Dendritic cell F-actin appears as dynamic foci that are nucleated by the Arp2/3 complex. WAVE ablated dendritic cells show increased membrane tension, leading to an altered ultrastructure of the immunological synapse and severe T cell priming defects. These results point towards a previously unappreciated role of the cellular mechanics of dendritic cells in T cell activation. Additionally, we present a novel cell culture based system for the differentiation of dendritic cells from conditionally immortalized hematopoietic precursors. These precursor cells are genetically tractable via the CRISPR/Cas9 system while they retain their ability to differentiate into highly migratory dendritic cells and other immune cells. This will foster the study of all aspects of dendritic cell biology and beyond.

Identification and characterization of novel auxin-cytokinin cross-talk components - Hurny, Andrej
The whole life cycle of plants as well as their responses to environmental stimuli is governed by a complex network of hormonal regulations. A number of studies have demonstrated an essential role of both auxin and cytokinin in the regulation of many aspects of plant growth and development including embryogenesis, postembryonic organogenic processes such as root, and shoot branching, root and shoot apical meristem activity and phyllotaxis. Over the last decades essential knowledge on the key molecular factors and pathways that spatio-temporally define auxin and cytokinin activities in the plant body has accumulated. However, how both hormonal pathways are interconnected by a complex network of interactions and feedback circuits that determines the final outcome of the individual hormone actions is still largely unknown. Root system architecture establishment and in particular formation of lateral organs is prime example of developmental process at whose regulation both auxin and cytokinin pathways converge. To dissect convergence points and pathways that tightly balance auxin - cytokinin antagonistic activities that determine the root branching pattern transcriptome profiling was applied. Genome wide expression analyses of the xylem pole pericycle, a tissue giving rise to lateral roots, led to identification of genes that are highly responsive to combinatorial auxin and cytokinin treatments and play an essential function in the auxin-cytokinin regulated root branching. SYNERGISTIC AUXIN CYTOKININ 1 (SYAC1) gene, which encodes for a protein of unknown function, was detected among the top candidate genes of which expression was synergistically up-regulated by simultaneous hormonal treatment. Plants with modulated SYAC1 activity exhibit severe defects in the root system establishment and attenuate developmental responses to both auxin and cytokinin. To explore the biological function of the SYAC1, we employed different strategies including expression pattern analysis, subcellular localization and phenotypic analyses of the syac1 loss-of-function and gain-of-function transgenic lines along with the identification of the SYAC1 interaction partners. Detailed functional characterization revealed that SYAC1 acts as a developmentally specific regulator of the secretory pathway to control deposition of cell wall components and thereby rapidly fine tune elongation growth.

Reactivation content is important for consolidation of spatial memory - Gridchyn, Igor
The hippocampus is a key brain region for spatial memory and navigation and is needed at all stages of memory, including encoding, consolidation, and recall. Hippocampal place cells selectively discharge at specific locations of the environment to form a cognitive map of the space. During the rest period and sleep following spatial navigation and/or learning, the waking activity of the place cells is reactivated within high synchrony events. This reactivation is thought to be important for memory consolidation and stabilization of the spatial representations. The aim of my thesis was to directly test whether the reactivation content encoded in firing patterns of place cells is important for consolidation of spatial memories. In particular, I aimed to test whether, in cases when multiple spatial memory traces are acquired during learning, the specific disruption of the reactivation of a subset of these memories leads to the selective disruption of the corresponding memory traces or through memory interference the other learned memories are disrupted as well. In this thesis, using a modified cheeseboard paradigm and a closed-loop recording setup with feedback optogenetic stimulation, I examined how the disruption of the reactivation of specific spiking patterns affects consolidation of the corresponding memory traces. To obtain multiple distinctive memories, animals had to perform a spatial task in two distinct cheeseboard environments and the reactivation of spiking patterns associated with one of the environments (target) was disrupted after learning during four hours rest period using a real-time decoding method. This real-time decoding method was capable of selectively affecting the firing rates and cofiring correlations of the target environment-encoding cells. The selective disruption led to behavioural impairment in the memory tests after the rest periods in the target environment but not in the other undisrupted control environment. In addition, the map of the target environment was less stable in the impaired memory tests compared to the learning session before than the map of the control environment. However, when the animal relearned the task, the same map recurred in the target environment that was present during learning before the disruption. Altogether my work demonstrated that the reactivation content is important: assembly-related disruption of reactivation can lead to a selective memory impairment and deficiency in map stability. These findings indeed suggest that reactivated assembly patterns reflect processes associated with the consolidation of memory traces.

Transcriptional regulation of macrophage migration in the Drosophila melanogaster embryo - Belyaeva, Vera
Immune cells migrating to the sites of infection navigate through diverse tissue architectures and switch their migratory mechanisms upon demand. However, little is known about systemic regulators that could allow the acquisition of these mechanisms. We performed a genetic screen in Drosophila melanogaster to identify regulators of germband invasion by embryonic macrophages into the confined space between the ectoderm and mesoderm. We have found that bZIP circadian transcription factors (TFs) Kayak (dFos) and Vrille (dNFIL3) have opposite effects on macrophage germband infiltration: Kayak facilitated and Vrille inhibited it. These TFs are enriched in the macrophages during migration and genetically interact to control it. Kayak sets a less coordinated mode of migration of the macrophage group and increases the probability and length of Levy walks. Intriguingly, the motility of kayak mutant macrophages was also strongly affected during initial germband invasion but not along another less confined route. Inhibiting Rho1 signaling within the tail ectoderm partially rescued the Kayak mutant phenotype, strongly suggesting that migrating macrophages have to overcome a barrier imposed by the stiffness of the ectoderm. Also, Kayak appeared to be important for the maintenance of the round cell shape and the rear edge translocation of the macrophages invading the germband. Complementary to this, the cortical actin cytoskeleton of Kayak- deficient macrophages was strongly affected. RNA sequencing revealed the filamin Cheerio and tetraspanin TM4SF to be downstream of Kayak. Chromatin immunoprecipitation and immunostaining revealed that the formin Diaphanous is another downstream target of Kayak. Immunostaining revealed that the formin Diaphanous is another downstream target of Kayak. Indeed, Cheerio, TM4SF and Diaphanous are required within macrophages for germband invasion, and expression of constitutively active Diaphanous in macrophages was able to rescue the kayak mutant phenotype. Moreover, Cher and Diaphanous are also reduced in the macrophages overexpressing Vrille. We hypothesize that Kayak, through its targets, increases actin polymerization and cortical tension in macrophages and thus allows extra force generation necessary for macrophage dissemination and migration through confined stiff tissues, while Vrille counterbalances it.

Design and characterization of methods and biological components to realize synthetic neurotransmission - Mckenzie, Catherine
A major challenge in neuroscience research is to dissect the circuits that orchestrate behavior in health and disease. Proteins from a wide range of non-mammalian species, such as microbial opsins, have been successfully transplanted to specific neuronal targets to override their natural communication patterns. The goal of our work is to manipulate synaptic communication in a manner that closely incorporates the functional intricacies of synapses by preserving temporal encoding (i.e. the firing pattern of the presynaptic neuron) and connectivity (i.e. target specific synapses rather than specific neurons). Our strategy to achieve this goal builds on the use of non-mammalian transplants to create a synthetic synapse. The mode of modulation comes from pre-synaptic uptake of a synthetic neurotransmitter (SN) into synaptic vesicles by means of a genetically targeted transporter selective for the SN. Upon natural vesicular release, exposure of the SN to the synaptic cleft will modify the post-synaptic potential through an orthogonal ligand gated ion channel. To achieve this goal we have functionally characterized a mixed cationic methionine-gated ion channel from Arabidopsis thaliana, designed a method to functionally characterize a synthetic transporter in isolated synaptic vesicles without the need for transgenic animals, identified and extracted multiple prokaryotic uptake systems that are substrate specific for methionine (Met), and established a primary/cell line co-culture system that would allow future combinatorial testing of this orthogonal transmitter-transporter-channel trifecta. Synthetic synapses will provide a unique opportunity to manipulate synaptic communication while maintaining the electrophysiological integrity of the pre-synaptic cell. In this way, information may be preserved that was generated in upstream circuits and that could be essential for concerted function and information processing.

Optogenetic Frizzled 7 reveals a permissive function of Wnt/PCP signaling in directed mesenchymal cell migration - Capek, Daniel
The Wnt/planar cell polarity (Wnt/PCP) pathway determines planar polarity of epithelial cells in both vertebrates and invertebrates. The role that Wnt/PCP signaling plays in mesenchymal contexts, however, is only poorly understood. While previous studies have demonstrated the capacity of Wnt/PCP signaling to polarize and guide directed migration of mesenchymal cells, it remains unclear whether endogenous Wnt/PCP signaling performs these functions instructively, as it does in epithelial cells. Here we developed a light-switchable version of the Wnt/PCP receptor Frizzled 7 (Fz7) to unambiguously distinguish between an instructive and a permissive role of Wnt/PCP signaling for the directional collective migration of mesendoderm progenitor cells during zebrafish gastrulation. We show that prechordal plate (ppl) cell migration is defective in maternal-zygotic fz7a and fz7b (MZ fz7a,b) double mutant embryos, and that Fz7 functions cell-autonomously in this process by promoting ppl cell protrusion formation and directed migration. We further show that local activation of Fz7 can direct ppl cell migration both in vitro and in vivo. Surprisingly, however, uniform Fz7 activation is sufficient to fully rescue the ppl cell migration defect in MZ fz7a,b mutant embryos, indicating that Wnt/PCP signaling functions permissively rather than instructively in directed mesendoderm cell migration during zebrafish gastrulation.

The influence of sequence context on the evolution of bacterial gene expression - Steinrück, Magdalena
Expression of genes is a fundamental molecular phenotype that is subject to evolution by different types of mutations. Both the rate and the effect of mutations may depend on the DNA sequence context of a particular gene or a particular promoter sequence. In this thesis I investigate the nature of this dependence using simple genetic systems in Escherichia coli. With these systems I explore the evolution of constitutive gene expression from random starting sequences at different loci on the chromosome and at different locations in sequence space. First, I dissect chromosomal neighborhood effects that underlie locus-dependent differences in the potential of a gene under selection to become more highly expressed. Next, I find that the effects of point mutations in promoter sequences are dependent on sequence context, and that an existing energy matrix model performs poorly in predicting relative expression of unrelated sequences. Finally, I show that a substantial fraction of random sequences contain functional promoters and I present an extended thermodynamic model that predicts promoter strength in full sequence space. Taken together, these results provide new insights and guides on how to integrate information on sequence context to improve our qualitative and quantitative understanding of bacterial gene expression, with implications for rapid evolution of drug resistance, de novo evolution of genes, and horizontal gene transfer.

30 GHz-voltage controlled oscillator operating at 4 K - Hollmann, Arne; Jirovec, Daniel; Kucharski, Maciej; Kissinger, Dietmar; Fischer, Gunter; Schreiber, Lars R. (Review of Scientific Instruments)
Solid-state qubit manipulation and read-out fidelities are reaching fault-tolerance, but quantum error correction requires millions of physical qubits and therefore a scalable quantum computer architecture. To solve signal-line bandwidth and fan-out problems, microwave sources required for qubit manipulation might be embedded close to the qubit chip, typically operating at temperatures below 4 K. Here, we perform the first low temperature measurements of a 130 nm BiCMOS based SiGe voltage controlled oscillator at cryogenic temperature. We determined the frequency and output power dependence on temperature and magnetic field up to 5 T and measured the temperature influence on its noise performance. The device maintains its full functionality from 300 K to 4 K. The carrier frequency at 4 K increases by 3% with respect to the carrier frequency at 300 K, and the output power at 4 K increases by 10 dB relative to the output power at 300 K. The frequency tuning range of approximately 20% remains unchanged between 300 K and 4 K. In an in-plane magnetic field of 5 T, the carrier frequency shifts by only 0.02% compared to the frequency at zero magnetic field.

Genetic determinants of antibiotic resistance evolution - Lukacisinova, Marta
Antibiotic resistance can emerge spontaneously through genomic mutation and render treatment ineffective. To counteract this process, in addition to the discovery and description of resistance mechanisms,a deeper understanding of resistanceevolvabilityand its determinantsis needed. To address this challenge, this thesisuncoversnew genetic determinants of resistance evolvability using a customized robotic setup, exploressystematic ways in which resistance evolution is perturbed due to dose-responsecharacteristics of drugs and mutation rate differences,and mathematically investigates the evolutionary fate of one specific type of evolvability modifier -a stress-induced mutagenesis allele.We find severalgenes which strongly inhibit or potentiate resistance evolution. In order to identify them, we first developedan automated high-throughput feedback-controlled protocol whichkeeps the population size and selection pressure approximately constant for hundreds of cultures by dynamically re-diluting the cultures and adjusting the antibiotic concentration. We implementedthis protocol on a customized liquid handling robot and propagated 100 different gene deletion strains of Escherichia coliin triplicate for over 100 generations in tetracycline and in chloramphenicol, and comparedtheir adaptation rates.We find a diminishing returns pattern, where initially sensitive strains adapted more compared to less sensitive ones. Our data uncover that deletions of certain genes which do not affect mutation rate,including efflux pump components, a chaperone and severalstructural and regulatory genes can strongly and reproducibly alterresistance evolution. Sequencing analysis of evolved populations indicates that epistasis with resistance mutations is the most likelyexplanation. This work could inspire treatment strategies in which targeted inhibitors of evolvability mechanisms will be given alongside antibiotics to slow down resistance evolution and extend theefficacy of antibiotics.We implemented astochasticpopulation genetics model, toverifyways in which general properties, namely, dose-response characteristics of drugs and mutation rates, influence evolutionary dynamics. In particular, under the exposure to antibiotics with shallow dose-response curves,bacteria have narrower distributions of fitness effects of new mutations. We show that in silicothis also leads to slower resistance evolution. We see and confirm with experiments that increased mutation rates, apart from speeding up evolution, also leadto high reproducibility of phenotypic adaptation in a context of continually strong selection pressure.Knowledge of these patterns can aid in predicting the dynamics of antibiotic resistance evolutionand adapting treatment schemes accordingly.Focusing on a previously described type of evolvability modifier –a stress-induced mutagenesis allele –we find conditions under which it can persist in a population under periodic selectionakin to clinical treatment. We set up a deterministic infinite populationcontinuous time model tracking the frequencies of a mutator and resistance allele and evaluate various treatment schemes in how well they maintain a stress-induced mutator allele. In particular,a high diversity of stresses is crucial for the persistence of the mutator allele. This leads to a general trade-off where exactly those diversifying treatment schemes which are likely to decrease levels of resistance could lead to stronger selection of highly evolvable genotypes.In the long run, this work will lead to a deeper understanding of the genetic and cellular mechanisms involved in antibiotic resistance evolution and could inspire new strategies for slowing down its rate.

Tools allowing independent visualization and genetic manipulation of Drosophila melanogaster macrophages and surrounding tissues - György, Attila; Roblek, Marko; Ratheesh, Aparna; Valosková, Katarina; Belyaeva, Vera; Wachner, Stephanie; Matsubayashi, Yutaka; Sanchez Sanchez, Besaiz; Stramer, Brian; Siekhaus, Daria E (G3: Genes, Genomes, Genetics)
Drosophila melanogaster plasmatocytes, the phagocytic cells among hemocytes, are essential for immune responses, but also play key roles from early development to death through their interactions with other cell types. They regulate homeostasis and signaling during development, stem cell proliferation, metabolism, cancer, wound responses and aging, displaying intriguing molecular and functional conservation with vertebrate macrophages. Given the relative ease of genetics in Drosophila compared to vertebrates, tools permitting visualization and genetic manipulation of plasmatocytes and surrounding tissues independently at all stages would greatly aid in fully understanding these processes, but are lacking. Here we describe a comprehensive set of transgenic lines that allow this. These include extremely brightly fluorescing mCherry-based lines that allow GAL4-independent visualization of plasmatocyte nuclei, cytoplasm or actin cytoskeleton from embryonic Stage 8 through adulthood in both live and fixed samples even as heterozygotes, greatly facilitating screening. These lines allow live visualization and tracking of embryonic plasmatocytes, as well as larval plasmatocytes residing at the body wall or flowing with the surrounding hemolymph. With confocal imaging, interactions of plasmatocytes and inner tissues can be seen in live or fixed embryos, larvae and adults. They permit efficient GAL4-independent FACS analysis/sorting of plasmatocytes throughout life. To facilitate genetic analysis of reciprocal signaling, we have also made a plasmatocyte-expressing QF2 line that in combination with extant GAL4 drivers allows independent genetic manipulation of both plasmatocytes and surrounding tissues, and a GAL80 line that blocks GAL4 drivers from affecting plasmatocytes, both of which function from the early embryo to the adult.

Differential association of GABAB receptors with their effector ion channels in Purkinje cells - Luján, Rafael; Aguado, Carolina; Ciruela, Francisco; Cózar, Javier; Kleindienst, David; De La Ossa, Luis; Bettler, Bernhard; Wickman, Kevin; Watanabe, Masahiko; Shigemoto, Ryuichi; Fukazawa, Yugo (Brain Structure and Function)
Metabotropic GABAB receptors mediate slow inhibitory effects presynaptically and postsynaptically through the modulation of different effector signalling pathways. Here, we analysed the distribution of GABAB receptors using highly sensitive SDS-digested freeze-fracture replica labelling in mouse cerebellar Purkinje cells. Immunoreactivity for GABAB1 was observed on presynaptic and, more abundantly, on postsynaptic compartments, showing both scattered and clustered distribution patterns. Quantitative analysis of immunoparticles revealed a somato-dendritic gradient, with the density of immunoparticles increasing 26-fold from somata to dendritic spines. To understand the spatial relationship of GABAB receptors with two key effector ion channels, the G protein-gated inwardly rectifying K+ (GIRK/Kir3) channel and the voltage-dependent Ca2+ channel, biochemical and immunohistochemical approaches were performed. Co-immunoprecipitation analysis demonstrated that GABAB receptors co-assembled with GIRK and CaV2.1 channels in the cerebellum. Using double-labelling immunoelectron microscopic techniques, co-clustering between GABAB1 and GIRK2 was detected in dendritic spines, whereas they were mainly segregated in the dendritic shafts. In contrast, co-clustering of GABAB1 and CaV2.1 was detected in dendritic shafts but not spines. Presynaptically, although no significant co-clustering of GABAB1 and GIRK2 or CaV2.1 channels was detected, inter-cluster distance for GABAB1 and GIRK2 was significantly smaller in the active zone than in the dendritic shafts, and that for GABAB1 and CaV2.1 was significantly smaller in the active zone than in the dendritic shafts and spines. Thus, GABAB receptors are associated with GIRK and CaV2.1 channels in different subcellular compartments. These data provide a better framework for understanding the different roles played by GABAB receptors and their effector ion channels in the cerebellar network.

Parvalbumin+ interneurons obey unique connectivity rules and establish a powerful lateral-inhibition microcircuit in dentate gyrus - Espinoza Martinez, Claudia; Guzmán, José; Zhang, Xiaomin; Jonas, Peter M (Nature Communications)
Parvalbumin-positive (PV+) GABAergic interneurons in hippocampal microcircuits are thought to play a key role in several higher network functions, such as feedforward and feedback inhibition, network oscillations, and pattern separation. Fast lateral inhibition mediated by GABAergic interneurons may implement a winner-takes-all mechanism in the hippocampal input layer. However, it is not clear whether the functional connectivity rules of granule cells (GCs) and interneurons in the dentate gyrus are consistent with such a mechanism. Using simultaneous patch-clamp recordings from up to seven GCs and up to four PV+ interneurons in the dentate gyrus, we find that connectivity is structured in space, synapse-specific, and enriched in specific disynaptic motifs. In contrast to the neocortex, lateral inhibition in the dentate gyrus (in which a GC inhibits neighboring GCs via a PV+ interneuron) is ~ 10-times more abundant than recurrent inhibition (in which a GC inhibits itself). Thus, unique connectivity rules may enable the dentate gyrus to perform specific higher-order computations

Ergodic mean-payoff games for the analysis of attacks in crypto-currencies - Chatterjee, Krishnendu; Goharshady, Amir; Ibsen-Jensen, Rasmus; Velner, Yaron
Crypto-currencies are digital assets designed to work as a medium of exchange, e.g., Bitcoin, but they are susceptible to attacks (dishonest behavior of participants). A framework for the analysis of attacks in crypto-currencies requires (a) modeling of game-theoretic aspects to analyze incentives for deviation from honest behavior; (b) concurrent interactions between participants; and (c) analysis of long-term monetary gains. Traditional game-theoretic approaches for the analysis of security protocols consider either qualitative temporal properties such as safety and termination, or the very special class of one-shot (stateless) games. However, to analyze general attacks on protocols for crypto-currencies, both stateful analysis and quantitative objectives are necessary. In this work our main contributions are as follows: (a) we show how a class of concurrent mean-payo games, namely ergodic games, can model various attacks that arise naturally in crypto-currencies; (b) we present the first practical implementation of algorithms for ergodic games that scales to model realistic problems for crypto-currencies; and (c) we present experimental results showing that our framework can handle games with thousands of states and millions of transitions.

Quantitative analysis of smart contracts - Chatterjee, Krishnendu; Goharshady, Amir; Velner, Yaron
Smart contracts are computer programs that are executed by a network of mutually distrusting agents, without the need of an external trusted authority. Smart contracts handle and transfer assets of considerable value (in the form of crypto-currency like Bitcoin). Hence, it is crucial that their implementation is bug-free. We identify the utility (or expected payoff) of interacting with such smart contracts as the basic and canonical quantitative property for such contracts. We present a framework for such quantitative analysis of smart contracts. Such a formal framework poses new and novel research challenges in programming languages, as it requires modeling of game-theoretic aspects to analyze incentives for deviation from honest behavior and modeling utilities which are not specified as standard temporal properties such as safety and termination. While game-theoretic incentives have been analyzed in the security community, their analysis has been restricted to the very special case of stateless games. However, to analyze smart contracts, stateful analysis is required as it must account for the different program states of the protocol. Our main contributions are as follows: we present (i)~a simplified programming language for smart contracts; (ii)~an automatic translation of the programs to state-based games; (iii)~an abstraction-refinement approach to solve such games; and (iv)~experimental results on real-world-inspired smart contracts.

Secure Credit Reporting on the Blockchain - Goharshady, Amir Kafshdar; Behrouz, Ali; Chatterjee, Krishnendu (Proceedings of the IEEE International Conference on Blockchain)
We present a secure approach for maintaining andreporting credit history records on the Blockchain. Our ap-proach removes third-parties such as credit reporting agen-cies from the lending process and replaces them with smartcontracts. This allows customers to interact directly with thelenders or banks while ensuring the integrity, unmalleabilityand privacy of their credit data. Additionally, each customerhas full control over complete or selective disclosure of hercredit records, eliminating the risk of privacy violations or databreaches. Moreover, our approach provides strong guaranteesfor the lenders as well. A lender can check both correctness andcompleteness of the credit data disclosed to her. This is the firstapproach that can perform all credit reporting tasks withouta central authority or changing the financial mechanisms*.

Algorithms for algebraic path properties in concurrent systems of constant treewidth components - Chatterjee, Krishnendu; Ibsen-Jensen, Rasmus; Goharshady, Amir Kafshdar; Pavlogiannis, Andreas (ACM Transactions on Programming Languages and Systems)
We study algorithmic questions wrt algebraic path properties in concurrent systems, where the transitions of the system are labeled from a complete, closed semiring. The algebraic path properties can model dataflow analysis problems, the shortest path problem, and many other natural problems that arise in program analysis. We consider that each component of the concurrent system is a graph with constant treewidth, a property satisfied by the controlflow graphs of most programs. We allow for multiple possible queries, which arise naturally in demand driven dataflow analysis. The study of multiple queries allows us to consider the tradeoff between the resource usage of the one-time preprocessing and for each individual query. The traditional approach constructs the product graph of all components and applies the best-known graph algorithm on the product. In this approach, even the answer to a single query requires the transitive closure (i.e., the results of all possible queries), which provides no room for tradeoff between preprocessing and query time. Our main contributions are algorithms that significantly improve the worst-case running time of the traditional approach, and provide various tradeoffs depending on the number of queries. For example, in a concurrent system of two components, the traditional approach requires hexic time in the worst case for answering one query as well as computing the transitive closure, whereas we show that with one-time preprocessing in almost cubic time, each subsequent query can be answered in at most linear time, and even the transitive closure can be computed in almost quartic time. Furthermore, we establish conditional optimality results showing that the worst-case running time of our algorithms cannot be improved without achieving major breakthroughs in graph algorithms (i.e., improving the worst-case bound for the shortest path problem in general graphs). Preliminary experimental results show that our algorithms perform favorably on several benchmarks.

Computational approaches for stochastic shortest path on succinct MDPs - Chatterjee, Krishnendu; Fu, Hongfei; Goharshady, Amir; Okati, Nastaran (Proceedings of the Twenty-Seventh International Joint Conference on Artificial Intelligence)
We consider the stochastic shortest path (SSP)problem for succinct Markov decision processes(MDPs), where the MDP consists of a set of vari-ables, and a set of nondeterministic rules that up-date the variables. First, we show that several ex-amples from the AI literature can be modeled assuccinct MDPs. Then we present computationalapproaches for upper and lower bounds for theSSP problem: (a) for computing upper bounds, ourmethod is polynomial-time in the implicit descrip-tion of the MDP; (b) for lower bounds, we present apolynomial-time (in the size of the implicit descrip-tion) reduction to quadratic programming. Our ap-proach is applicable even to infinite-state MDPs.Finally, we present experimental results to demon-strate the effectiveness of our approach on severalclassical examples from the AI literature.

Relaminarization by steady modification of the streamwise velocity profile in a pipe - Kühnen, Jakob; Scarselli, Davide; Schaner, Markus; Hof, Björn (Flow Turbulence and Combustion)
We show that a rather simple, steady modification of the streamwise velocity profile in a pipe can lead to a complete collapse of turbulence and the flow fully relaminarizes. Two different devices, a stationary obstacle (inset) and a device which injects fluid through an annular gap close to the wall, are used to control the flow. Both devices modify the streamwise velocity profile such that the flow in the center of the pipe is decelerated and the flow in the near wall region is accelerated. We present measurements with stereoscopic particle image velocimetry to investigate and capture the development of the relaminarizing flow downstream these devices and the specific circumstances responsible for relaminarization. We find total relaminarization up to Reynolds numbers of 6000, where the skin friction in the far downstream distance is reduced by a factor of 3.4 due to relaminarization. In a smooth straight pipe the flow remains completely laminar downstream of the control. Furthermore, we show that transient (temporary) relaminarization in a spatially confined region right downstream the devices occurs also at much higher Reynolds numbers, accompanied by a significant local skin friction drag reduction. The underlying physical mechanism of relaminarization is attributed to a weakening of the near-wall turbulence production cycle.

Destabilizing turbulence in pipe flow - Kühnen, Jakob; Song, Baofang; Scarselli, Davide; Budanur, Nazmi B; Riedl, Michael; Willis, Ashley; Avila, Marc; Hof, Björn (Nature Physics)
Turbulence is the major cause of friction losses in transport processes and it is responsible for a drastic drag increase in flows over bounding surfaces. While much effort is invested into developing ways to control and reduce turbulence intensities, so far no methods exist to altogether eliminate turbulence if velocities are sufficiently large. We demonstrate for pipe flow that appropriate distortions to the velocity profile lead to a complete collapse of turbulence and subsequently friction losses are reduced by as much as 90%. Counterintuitively, the return to laminar motion is accomplished by initially increasing turbulence intensities or by transiently amplifying wall shear. Since neither the Reynolds number nor the shear stresses decrease (the latter often increase), these measures are not indicative of turbulence collapse. Instead, an amplification mechanism measuring the interaction between eddies and the mean shear is found to set a threshold below which turbulence is suppressed beyond recovery.

WRKY23 is a component of the transcriptional network mediating auxin feedback on PIN polarity - Prat, Tomas; Hajny, Jakub; Grunewald, Wim; Vasileva, Mina K; Molnar, Gergely; Tejos, Ricardo; Schmid, Markus; Sauer, Michael; Friml, Jirí (PLoS Genetics)
Auxin is unique among plant hormones due to its directional transport that is mediated by the polarly distributed PIN auxin transporters at the plasma membrane. The canalization hypothesis proposes that the auxin feedback on its polar flow is a crucial, plant-specific mechanism mediating multiple self-organizing developmental processes. Here, we used the auxin effect on the PIN polar localization in Arabidopsis thaliana roots as a proxy for the auxin feedback on the PIN polarity during canalization. We performed microarray experiments to find regulators of this process that act downstream of auxin. We identified genes that were transcriptionally regulated by auxin in an AXR3/IAA17- and ARF7/ARF19-dependent manner. Besides the known components of the PIN polarity, such as PID and PIP5K kinases, a number of potential new regulators were detected, among which the WRKY23 transcription factor, which was characterized in more detail. Gain- and loss-of-function mutants confirmed a role for WRKY23 in mediating the auxin effect on the PIN polarity. Accordingly, processes requiring auxin-mediated PIN polarity rearrangements, such as vascular tissue development during leaf venation, showed a higher WRKY23 expression and required the WRKY23 activity. Our results provide initial insights into the auxin transcriptional network acting upstream of PIN polarization and, potentially, canalization-mediated plant development.

PID/WAG-mediated phosphorylation of the Arabidopsis PIN3 auxin transporter mediates polarity switches during gravitropism - Grones, Peter; Abas, Melinda F; Hajny, Jakub; Jones, Angharad; Waidmann, Sascha; Kleine Vehn, Jürgen; Friml, Jirí (Scientific Reports)
Intercellular distribution of the plant hormone auxin largely depends on the polar subcellular distribution of the plasma membrane PIN-FORMED (PIN) auxin transporters. PIN polarity switches in response to different developmental and environmental signals have been shown to redirect auxin fluxes mediating certain developmental responses. PIN phosphorylation at different sites and by different kinases is crucial for PIN function. Here we investigate the role of PIN phosphorylation during gravitropic response. Loss- and gain-of-function mutants in PINOID and related kinases but not in D6PK kinase as well as mutations mimicking constitutive dephosphorylated or phosphorylated status of two clusters of predicted phosphorylation sites partially disrupted PIN3 phosphorylation and caused defects in gravitropic bending in roots and hypocotyls. In particular, they impacted PIN3 polarity rearrangements in response to gravity and during feed-back regulation by auxin itself. Thus PIN phosphorylation, besides regulating transport activity and apical-basal targeting, is also important for the rapid polarity switches in response to environmental and endogenous signals.

Chemokines and integrins independently tune actin flow and substrate friction during intranodal migration of T cells - Hons, Miroslav; Kopf, Aglaja; Hauschild, Robert; Leithner, Alexander F; Gärtner, Florian R; Abe, Jun; Renkawitz, Jörg; Stein, Jens; Sixt, Michael K (Nature Immunology)
Although much is known about the physiological framework of T cell motility, and numerous rate-limiting molecules have been identified through loss-of-function approaches, an integrated functional concept of T cell motility is lacking. Here, we used in vivo precision morphometry together with analysis of cytoskeletal dynamics in vitro to deconstruct the basic mechanisms of T cell migration within lymphatic organs. We show that the contributions of the integrin LFA-1 and the chemokine receptor CCR7 are complementary rather than positioned in a linear pathway, as they are during leukocyte extravasation from the blood vasculature. Our data demonstrate that CCR7 controls cortical actin flows, whereas integrins mediate substrate friction that is sufficient to drive locomotion in the absence of considerable surface adhesions and plasma membrane flux.

Real-time analysis of auxin response, cell wall pH and elongation in Arabidopsis thaliana Hypocotyls - Li, Lanxin; Krens, Gabriel; Fendrych, Matyas; Friml, Jirí (Bio-protocol)
The rapid auxin-triggered growth of the Arabidopsis hypocotyls involves the nuclear TIR1/AFB-Aux/IAA signaling and is accompanied by acidification of the apoplast and cell walls (Fendrych et al., 2016). Here, we describe in detail the method for analysis of the elongation and the TIR1/AFB-Aux/IAA-dependent auxin response in hypocotyl segments as well as the determination of relative values of the cell wall pH.

Haploinsufficiency of the intellectual disability gene SETD5 disturbs developmental gene expression and cognition - Deliu, Elena; Arecco, Niccoló; Morandell, Jasmin; Dotter, Christoph; Contreras, Ximena; Girardot, Charles; Käsper, Eva; Kozlova, Alena; Kishi, Kasumi; Chiaradia, Ilaria; Noh, Kyung; Novarino, Gaia (Nature Neuroscience)
SETD5 gene mutations have been identified as a frequent cause of idiopathic intellectual disability. Here we show that Setd5-haploinsufficient mice present developmental defects such as abnormal brain-to-body weight ratios and neural crest defect-associated phenotypes. Furthermore, Setd5-mutant mice show impairments in cognitive tasks, enhanced long-term potentiation, delayed ontogenetic profile of ultrasonic vocalization, and behavioral inflexibility. Behavioral issues are accompanied by abnormal expression of postsynaptic density proteins previously associated with cognition. Our data additionally indicate that Setd5 regulates RNA polymerase II dynamics and gene transcription via its interaction with the Hdac3 and Paf1 complexes, findings potentially explaining the gene expression defects observed in Setd5-haploinsufficient mice. Our results emphasize the decisive role of Setd5 in a biological pathway found to be disrupted in humans with intellectual disability and autism spectrum disorder.

Indirect reciprocity with private, noisy, and incomplete information - Hilbe, Christian; Schmid, Laura; Tkadlec, Josef; Chatterjee, Krishnendu; Nowak, Martin (PNAS)
Indirect reciprocity explores how humans act when their reputation is at stake, and which social norms they use to assess the actions of others. A crucial question in indirect reciprocity is which social norms can maintain stable cooperation in a society. Past research has highlighted eight such norms, called “leading-eight” strategies. This past research, however, is based on the assumption that all relevant information about other population members is publicly available and that everyone agrees on who is good or bad. Instead, here we explore the reputation dynamics when information is private and noisy. We show that under these conditions, most leading-eight strategies fail to evolve. Those leading-eight strategies that do evolve are unable to sustain full cooperation.Indirect reciprocity is a mechanism for cooperation based on shared moral systems and individual reputations. It assumes that members of a community routinely observe and assess each other and that they use this information to decide who is good or bad, and who deserves cooperation. When information is transmitted publicly, such that all community members agree on each other’s reputation, previous research has highlighted eight crucial moral systems. These “leading-eight” strategies can maintain cooperation and resist invasion by defectors. However, in real populations individuals often hold their own private views of others. Once two individuals disagree about their opinion of some third party, they may also see its subsequent actions in a different light. Their opinions may further diverge over time. Herein, we explore indirect reciprocity when information transmission is private and noisy. We find that in the presence of perception errors, most leading-eight strategies cease to be stable. Even if a leading-eight strategy evolves, cooperation rates may drop considerably when errors are common. Our research highlights the role of reliable information and synchronized reputations to maintain stable moral systems.

Evolutionary potential of transcription factors for gene regulatory rewiring - Igler, Claudia; Lagator, Mato; Tkacik, Gasper; Bollback, Jonathan P; Guet, Calin C (Nature Ecology and Evolution)
Gene regulatory networks evolve through rewiring of individual components—that is, through changes in regulatory connections. However, the mechanistic basis of regulatory rewiring is poorly understood. Using a canonical gene regulatory system, we quantify the properties of transcription factors that determine the evolutionary potential for rewiring of regulatory connections: robustness, tunability and evolvability. In vivo repression measurements of two repressors at mutated operator sites reveal their contrasting evolutionary potential: while robustness and evolvability were positively correlated, both were in trade-off with tunability. Epistatic interactions between adjacent operators alleviated this trade-off. A thermodynamic model explains how the differences in robustness, tunability and evolvability arise from biophysical characteristics of repressor–DNA binding. The model also uncovers that the energy matrix, which describes how mutations affect repressor–DNA binding, encodes crucial information about the evolutionary potential of a repressor. The biophysical determinants of evolutionary potential for regulatory rewiring constitute a mechanistic framework for understanding network evolution.

Data for the paper Evolutionary potential of transcription factors for gene regulatory rewiring - Igler, Claudia; Lagator, Mato; Tkacik, Gasper; Bollback, Jonathan P; Guet, Calin C
Mean repression values and standard error of the mean are given for all operator mutant libraries.

Tetrode recording from the hippocampus of behaving mice coupled with four-point-irradiation closed-loop optogenetics: A technique to study the contribution of Hippocampal SWR events to learning - Rangel Guerrero, Dámaris K; Donnett, James G.; Csicsvari, Jozsef L; Kovács, Krisztián (eNeuro)
With the advent of optogenetics, it became possible to change the activity of a targeted population of neurons in a temporally controlled manner. To combine the advantages of 60-channel in vivo tetrode recording and laser-based optogenetics, we have developed a closed-loop recording system that allows for the actual electrophysiological signal to be used as a trigger for the laser light mediating the optogenetic intervention. We have optimized the weight, size, and shape of the corresponding implant to make it compatible with the size, force, and movements of a behaving mouse, and we have shown that the system can efficiently block sharp wave ripple (SWR) events using those events themselves as a trigger. To demonstrate the full potential of the optogenetic recording system we present a pilot study addressing the contribution of SWR events to learning in a complex behavioral task.

Viewpoint: Microwave quantum states beat the heat - Fink, Johannes M (Physics)
From microwave ovens to satellite television to the GPS and data services on our mobile phones, microwave technology is everywhere today. But one technology that has so far failed to prove its worth in this wavelength regime is quantum communication that uses the states of single photons as information carriers. This is because single microwave photons, as opposed to classical microwave signals, are extremely vulnerable to noise from thermal excitations in the channels through which they travel. Two new independent studies, one by Ze-Liang Xiang at Technische Universität Wien (Vienna), Austria, and colleagues [1] and another by Benoît Vermersch at the University of Innsbruck, also in Austria, and colleagues [2] now describe a theoretical protocol for microwave quantum communication that is resilient to thermal and other types of noise. Their approach could become a powerful technique to establish fast links between superconducting data processors in a future all-microwave quantum network.

A new proof rule for almost-sure termination - Mciver, Annabelle; Morgan, Carroll; Kaminski, Benjamin Lucien; Katoen, Joost P (Proceedings of the ACM on Programming Languages)
We present a new proof rule for proving almost-sure termination of probabilistic programs, including those that contain demonic non-determinism. An important question for a probabilistic program is whether the probability mass of all its diverging runs is zero, that is that it terminates "almost surely". Proving that can be hard, and this paper presents a new method for doing so. It applies directly to the program's source code, even if the program contains demonic choice. Like others, we use variant functions (a.k.a. "super-martingales") that are real-valued and decrease randomly on each loop iteration; but our key innovation is that the amount as well as the probability of the decrease are parametric. We prove the soundness of the new rule, indicate where its applicability goes beyond existing rules, and explain its connection to classical results on denumerable (non-demonic) Markov chains.

Cumulative space in black-white pebbling and resolution - Alwen, Joel F; De Rezende, Susanna; Nordstrom, Jakob; Vinyals, Marc
We study space complexity and time-space trade-offs with a focus not on peak memory usage but on overall memory consumption throughout the computation. Such a cumulative space measure was introduced for the computational model of parallel black pebbling by [Alwen and Serbinenko ’15] as a tool for obtaining results in cryptography. We consider instead the non- deterministic black-white pebble game and prove optimal cumulative space lower bounds and trade-offs, where in order to minimize pebbling time the space has to remain large during a significant fraction of the pebbling. We also initiate the study of cumulative space in proof complexity, an area where other space complexity measures have been extensively studied during the last 10–15 years. Using and extending the connection between proof complexity and pebble games in [Ben-Sasson and Nordström ’08, ’11] we obtain several strong cumulative space results for (even parallel versions of) the resolution proof system, and outline some possible future directions of study of this, in our opinion, natural and interesting space measure.

Existence of traveling waves for the generalized F–KPP equation - Kollár, Richard; Novak, Sebastian (Bulletin of Mathematical Biology)
Variation in genotypes may be responsible for differences in dispersal rates, directional biases, and growth rates of individuals. These traits may favor certain genotypes and enhance their spatiotemporal spreading into areas occupied by the less advantageous genotypes. We study how these factors influence the speed of spreading in the case of two competing genotypes under the assumption that spatial variation of the total population is small compared to the spatial variation of the frequencies of the genotypes in the population. In that case, the dynamics of the frequency of one of the genotypes is approximately described by a generalized Fisher–Kolmogorov–Petrovskii–Piskunov (F–KPP) equation. This generalized F–KPP equation with (nonlinear) frequency-dependent diffusion and advection terms admits traveling wave solutions that characterize the invasion of the dominant genotype. Our existence results generalize the classical theory for traveling waves for the F–KPP with constant coefficients. Moreover, in the particular case of the quadratic (monostable) nonlinear growth–decay rate in the generalized F–KPP we study in detail the influence of the variance in diffusion and mean displacement rates of the two genotypes on the minimal wave propagation speed.

Unstable manifolds of relative periodic orbits in the symmetry reduced state space of the Kuramoto–Sivashinsky system - Budanur, Nazmi B; Cvitanović, Predrag (Journal of Statistical Physics)
Systems such as fluid flows in channels and pipes or the complex Ginzburg–Landau system, defined over periodic domains, exhibit both continuous symmetries, translational and rotational, as well as discrete symmetries under spatial reflections or complex conjugation. The simplest, and very common symmetry of this type is the equivariance of the defining equations under the orthogonal group O(2). We formulate a novel symmetry reduction scheme for such systems by combining the method of slices with invariant polynomial methods, and show how it works by applying it to the Kuramoto–Sivashinsky system in one spatial dimension. As an example, we track a relative periodic orbit through a sequence of bifurcations to the onset of chaos. Within the symmetry-reduced state space we are able to compute and visualize the unstable manifolds of relative periodic orbits, their torus bifurcations, a transition to chaos via torus breakdown, and heteroclinic connections between various relative periodic orbits. It would be very hard to carry through such analysis in the full state space, without a symmetry reduction such as the one we present here.

Hanani-Tutte for radial planarity - Fulek, Radoslav; Pelsmajer, Michael; Schaefer, Marcus (Journal of Graph Algorithms and Applications)
A drawing of a graph G is radial if the vertices of G are placed on concentric circles C 1 , . . . , C k with common center c , and edges are drawn radially : every edge intersects every circle centered at c at most once. G is radial planar if it has a radial embedding, that is, a crossing-free radial drawing. If the vertices of G are ordered or partitioned into ordered levels (as they are for leveled graphs), we require that the assignment of vertices to circles corresponds to the given ordering or leveling. We show that a graph G is radial planar if G has a radial drawing in which every two edges cross an even number of times; the radial embedding has the same leveling as the radial drawing. In other words, we establish the weak variant of the Hanani-Tutte theorem for radial planarity. This generalizes a result by Pach and Toth.

Ensembles of bidirectional kinesin Cin8 produce additive forces in both directions of movement - Fallesen, Todd; Roostalu, Johanna; Düllberg, Christian F; Pruessner, Gunnar; Surrey, Thomas (Biophysical Journal)
Most kinesin motors move in only one direction along microtubules. Members of the kinesin-5 subfamily were initially described as unidirectional plus-end-directed motors and shown to produce piconewton forces. However, some fungal kinesin-5 motors are bidirectional. The force production of a bidirectional kinesin-5 has not yet been measured. Therefore, it remains unknown whether the mechanism of the unconventional minus-end-directed motility differs fundamentally from that of plus-end-directed stepping. Using force spectroscopy, we have measured here the forces that ensembles of purified budding yeast kinesin-5 Cin8 produce in microtubule gliding assays in both plus- and minus-end direction. Correlation analysis of pause forces demonstrated that individual Cin8 molecules produce additive forces in both directions of movement. In ensembles, Cin8 motors were able to produce single-motor forces up to a magnitude of ∼1.5 pN. Hence, these properties appear to be conserved within the kinesin-5 subfamily. Force production was largely independent of the directionality of movement, indicating similarities between the motility mechanisms for both directions. These results provide constraints for the development of models for the bidirectional motility mechanism of fission yeast kinesin-5 and provide insight into the function of this mitotic motor.

Improved algorithms for parity and Streett objectives - Chatterjee, Krishnendu; Henzinger, Monika H; Loitzenbauer, Veronika (Logical Methods in Computer Science)
The computation of the winning set for parity objectives and for Streett objectives in graphs as well as in game graphs are central problems in computer-aided verification, with application to the verification of closed systems with strong fairness conditions, the verification of open systems, checking interface compatibility, well-formedness of specifications, and the synthesis of reactive systems. We show how to compute the winning set on n vertices for (1) parity-3 (aka one-pair Streett) objectives in game graphs in time O(n5/2) and for (2) k-pair Streett objectives in graphs in time O(n2+nklogn). For both problems this gives faster algorithms for dense graphs and represents the first improvement in asymptotic running time in 15 years.

Water wave packets - Jeschke, Stefan; Wojtan, Christopher J (ACM Transactions on Graphics)
This paper presents a method for simulating water surface waves as a displacement field on a 2D domain. Our method relies on Lagrangian particles that carry packets of water wave energy; each packet carries information about an entire group of wave trains, as opposed to only a single wave crest. Our approach is unconditionally stable and can simulate high resolution geometric details. This approach also presents a straightforward interface for artistic control, because it is essentially a particle system with intuitive parameters like wavelength and amplitude. Our implementation parallelizes well and runs in real time for moderately challenging scenarios.

Faster statistical model checking for unbounded temporal properties - Daca, Przemyslaw; Henzinger, Thomas A; Kretinsky, Jan; Petrov, Tatjana (ACM Transactions on Computational Logic (TOCL))
We present a new algorithm for the statistical model checking of Markov chains with respect to unbounded temporal properties, including full linear temporal logic. The main idea is that we monitor each simulation run on the fly, in order to detect quickly if a bottom strongly connected component is entered with high probability, in which case the simulation run can be terminated early. As a result, our simulation runs are often much shorter than required by termination bounds that are computed a priori for a desired level of confidence on a large state space. In comparison to previous algorithms for statistical model checking our method is not only faster in many cases but also requires less information about the system, namely, only the minimum transition probability that occurs in the Markov chain. In addition, our method can be generalised to unbounded quantitative properties such as mean-payoff bounds.

Planar matchings for weighted straight skeletons - Biedl, Therese; Huber, Stefan; Palfrader, Peter (International Journal of Computational Geometry and Applications)
We introduce planar matchings on directed pseudo-line arrangements, which yield a planar set of pseudo-line segments such that only matching-partners are adjacent. By translating the planar matching problem into a corresponding stable roommates problem we show that such matchings always exist. Using our new framework, we establish, for the first time, a complete, rigorous definition of weighted straight skeletons, which are based on a so-called wavefront propagation process. We present a generalized and unified approach to treat structural changes in the wavefront that focuses on the restoration of weak planarity by finding planar matchings.

Bogoliubov correction to the mean-field dynamics of interacting bosons - Nam, Phan; Napiórkowski, Marcin M (Advances in Theoretical and Mathematical Physics)
We consider the dynamics of a large quantum system of N identical bosons in 3D interacting via a two-body potential of the form N3β-1w(Nβ(x - y)). For fixed 0 = β < 1/3 and large N, we obtain a norm approximation to the many-body evolution in the Nparticle Hilbert space. The leading order behaviour of the dynamics is determined by Hartree theory while the second order is given by Bogoliubov theory.

Universality for a class of random band matrices - Bourgade, Paul; Erdös, László; Yau, Horng; Yin, Jun (Advances in Theoretical and Mathematical Physics)
We prove the universality for the eigenvalue gap statistics in the bulk of the spectrum for band matrices, in the regime where the band width is comparable with the dimension of the matrix, W ~ N. All previous results concerning universality of non-Gaussian random matrices are for mean-field models. By relying on a new mean-field reduction technique, we deduce universality from quantum unique ergodicity for band matrices.